hCG orchestrates ovulation in swamp eel (Monopterus albus) via progesterone, metabolic reprogramming, and pyroptosis - Mingsen Zhou; Linlin Wang; Shuo Zheng; Anfu Shen; Xuewen Rao; Liang Ke; Wenhao Hu; Changqing Han; Xiangjiang Liu; Guangfu Hu (Aquaculture, 2027)

IFI6 is associated with interferon activation and complement-associated immune responses in primary Sjögren’s disease - Yibing Han; Yikun Mei; Xiaoqin Meng; Minjv Zhang; Shuo Yang; Weizhi Wang; Wen Qiu; Zuoqing Dong (Functional & Integrative Genomics, 2026)

High expression of formin-2 can promote ovarian cancer chemoresistance via immunosuppressive macrophages - Shuo Feng; Yaping Wang; Ran Ren; Xiaotong Wang; Lu Han (Functional & Integrative Genomics, 2026)

Improving multi-view video fusion and model generalization in pig behavior monitoring with teacher–student semi-supervised learning - Shuo Wan; Junkai Li; Feiyue Xue; Tao Han; Ying Sha; Li Qin (Computers and Electronics in Agriculture, 2026)

TBBPA facilitates splenic inflammation and pyroptosis by targeting HMGB1 - Fu-Wei Jiang; Jing-Han Lin; Jia-Xin Wang; Ming-Shan Chen; Shuo Liu; Hong-Mei Zhu; Yu-Sheng Shi; Ming Lou; Zi-Yan Hu; Yi Zhao; Jin-Long Li (Journal of Environmental Sciences, 2026)

Energy absorption and structural optimization of plum multi-cell tubes with origami - Yue Zhou; Minsi Ji; Shuo Han; Zhuangzhuang Li; Zonglai Mo; Jun Li (Engineering Structures, 2026)

Competitive adsorption, nanoconfined occurrence states and theoretical CO₂-enhanced methane displacement in deep coal: Experimental investigation and SLD–PR modeling - Lei Han; Lili Wei; Jian Shen; Qian Wang; Xiaodong Zhang; Xiaoming Ni; Xiao Liu; Shuo Zhang (Chemical Engineering Journal, 2026)

Enhancing sulfur‑iron synergistic denitrification with sugar-liquor-absorbed activated carbon: Performance and mechanisms - Shuo Qiu; Xu Zhang; Lei Zhang; Jiacun Zhou; Zehao Shen; Mingyu Han; Zhibin Zhang (Journal of Water Process Engineering, 2026)

Straw return enhances soil multifunctionality and maize yield through shifts in bacterial community structure - Shijie Deng; Yang Yu; Yubo Hao; Yubo Jiang; Guoyi Lv; Yiteng Zhang; Linjing Han; Meng Cheng; Shuo Zhang; Chunrong Qian (Field Crops Research, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

A 5-HT-loaded coacervate biomaterial synergizing anti-inflammatory, antimicrobial, and antioxidant functions for accelerated infected wound healing - Zhengnan Zhao; Yinxuan Xu; Chengzhen Chu; Xueyang Li; Yang Shen; Xiaohan Liu; Xuesheng Zhang; Xincheng Tang; Tao Li; Shuo Chen; Chuanglong He; Wenhui Liu; et al. (Chemical Engineering Journal, 2026)

Enhanced phenanthrene degradation in microalgae-bacteria systems: Mechanistic roles of exogenous and indigenous degraders - Mengying Wang; Han Wang; Xuetao Liang; Jingran Li; Chen Wang; Longyan Cui; Shuo Yang; Jiaxuan Lin; Qi Yang; Zhilin Yang (Bioresource Technology, 2026)

Adsorption of sulfonamide antibiotics by phosphoric acid-activated passion fruit peel biochar and its plasma regeneration - Yiqin He; Shuo Wang; Haojie Li; Zimo Han; Xinpeng Liu; Qingmei Meng; Jiwei Li (Journal of Water Process Engineering, 2026)

A critical evaluation of water balance in the Yellow River Source Region - Boya Han; Yuefei Huang; Shuo Zhang (Journal of Hydrology, 2026)

Engineering synergistic VO–Co3+ pairs in CoOOH nanosheets for highly efficient and selective catalytic ozonation of CVOCs - Ke Zhang; Yaxin Zhao; Ji Li; Bingzheng Wang; Shuo Wang; Linkai Han; Jinze Lyu (Journal of Hazardous Materials, 2026)

AI-2 type quorum-sensing signal enhances mercury resistance and adsorption in thermotolerant Bacillus subtilis - Shuo Han; Qianyun Mo; Xiaobin Wen; Xiangru Wang; Xiangqian Wang; Yao Yu; Yixiao Yang; Chunzhe Yang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

Function identification of nitrogen forms in nitrogen-doped biochar for promoting methane production in anaerobic digestion - Xiao-Yue Cao; Cong-Cong Tang; Shuo-Han Chen; Sheng-Jie Sun; Chun-Xue Yang; Ai-Juan Zhou; Zewei Liu; Zhang-Wei He (Environmental Research, 2026)

PD-1/PD-L1 inhibition after cryoablation is associated with improved tumor control and immunosuppressive microenvironment remodeling in Lewis lung adenocarcinoma - Qi Liu; Shuo Zhang; Xuxin Chen; Jiao Li; Man Qi; Yongqun Li; Yiwei Ding; Xiaoyu Zhao; Jun Shi; Jiajia Tang; Meng Liu; Xue Wang; et al. (Cryobiology, 2026)

A novel phosphorylated chitin-hydroxyapatite composite promotes angiogenesis and osteogenesis for bone defect repair - Zhen Jiang; Siheng Niu; Wei Zhang; Zhiwen Jiang; Jinhua Chi; Shouriu Liu; Wanshun Liu; Shuo Wang; Baoqin Han (Carbohydrate Polymers, 2026)

Interactive Toxic Impacts of Thermal Stress and Residual Chlorine on Growth, Nutritional Composition and Digestive Physiology in Meretrix meretrix - Shuai Han; Sitong Wang; Haopeng Hu; Wenping Yang; Shuo Qin; Peng Gao; Yanming Sui; Yebing Yu; Mei Jiang; Lei Li (Fishes, 2026)
Thermal elevation and residual chlorine pollution are two anthropogenic stressors that co-occur in estuarine waters affected by coastal power plant effluents. A 30-day exposure experiment was established with six treatment combinations comprising three temperatures (27 °C, 28 °C, and 30 °C) and two residual chlorine concentrations (0 mg/L and 0.02 mg/L) on Meretrix meretrix. Sampling was conducted on days 0, 10, 20 and 30 of the trial. The results indicated that elevated temperature (30 °C) significantly suppressed shell height and total body weight, while residual chlorine (0.02 mg/L) exerted time-dependent effects on shell length and width, with a significant interactive effect on shell length only at day 30. Crude lipid content declined with increasing temperature and residual chlorine exposure, whereas moisture and ash contents showed significant two-way interactions at all sampling time points. Intestinal amylase activity was continuously regulated by both stressors, with interactive responses on days 10 and 20, and was significantly suppressed under combined high temperature and residual chlorine stress. Collectively, we infer that combined exposure to elevated temperature and residual chlorine impairs shell growth, muscle biochemical composition and intestinal amylase activity of M. meretrix. Long-term experiments are required to further clarify the joint toxic effects of thermal stress and residual chlorine on the clam species.

Rhizosphere inoculation with Streptomyces pactum is associated with sugar-related fruit quality and rhizosphere variation in goji berry (Lycium barbarum L.) - Yaping Ma; Jie Cao; Ping Yang; Yusupu Wayiti; Shuo Han; Kelong Wang; Alimire Ailimujiang; Yue Zhang (Plant and Soil, 2026)

Resveratrol alleviated inflammatory responses induced by cytopathic bovine viral diarrhea virus infection via NLRP3 inflammasome induced pyroptosis - Yang Han; Zhaofeng Zhang; Fenghua Jiang; Xinli Song; Shuo Jia; Yixin Lu (The Veterinary Journal, 2026)

The cytokinin oxidase/dehydrogenase MdCKX4 regulates drought tolerance in Malus domestica - Tong Li; Yu-Feng Zhang; Joy Xin-Yue Zhai; Zi-Quan Feng; Shuo Ma; Xin-Yi Li; Huai-Na Gao; Long-Xin Luo; Zhi Li; Qi Zhang; Min-Min Zhou; Ya-Li Zhang; et al. (Plant Science, 2026)

Triple-responsive supramolecular hydrogel with synergistic photothermal effect regulates inflammatory signaling to remodel the diabetic wound microenvironment and promote chronic wound healing - Jishang Sun; Jingwen Wang; Junfeng Ai; Ruxin Wang; Yanru Diao; Baoqin Han; Qingqing Bi; Jing Chang; Shuo Wang (Chemical Engineering Journal, 2026)

Automatic Detection and Rejection of Defective Potatoes and Impurities Using Machine Vision and a Sorting System - Danyang Lv; Tao Zhang; Minsheng Wu; Ranbing Yang; Jian Zhang; Qimin Liang; Shuo Han (Potato Research, 2026)

Microbial remediation of PAHs in aquatic environments: advances, ssynergistic mechanisms, and emerging strategies - Shuo Yang; Mengying Wang; Han Wang; Qi Yang; Zhilin Yang (Archives of Microbiology, 2026)

Genome-wide identification and expression analysis of the pectate lyase (PEL) gene family in soybean (Glycine max (L.) Merr. ) - Shuo Wu; Wanqing Du; Yu Han; Zhenggang Wang; Yujuan Gu; Xianlong Ding; Shouping Yang (Genetica, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Target-oriented molecularly imprinted polymers enable rapid ambient ionization mass spectrometric analysis of trace tetrachlorobisphenol a in environmental samples - Ya Jiao; Shuo Gao; Xiaoxuan Han; Yong Tian; Xiaoxu Huo; Jianwei Zhao; Xiaofeng Dong; Chunguang Liu; Weiliang Wang; Guifen Zhu; Xuwei Chen; Ming-Li Chen (Journal of Hazardous Materials, 2026)

Boosting aqueous Zn-ion battery performance with Co2+-doped δ-MnO2/Ti3C2Tx cathode through enhanced ion transport and structural stabilization - Shuo Li; Jing Zhu; Longkun Wu; Yasong Han; Ningning Zhao; Bin Li; Shaaban M. Shaaban; Lei Dai; Ling Wang; Zhangxing He (Chemical Engineering Journal, 2026)

Botryosphaeria dothidea: comprehensive understanding of its pathogenicity, resistance mechanisms, and management strategies in apple cultivation - Peng-Liang Han; Hou-Chao Wang; Hao Wu; Shuo-Chen Chai; Si-Qi Xu; Lei Yu; Da-Gang Hu (Planta, 2026)

Highly sensitive H2O2 colorimetric sensing in tumor cells via stable phospholipid-coated CsCu2I3 peroxidase-like nanoenzyme - Jiatong Wang; Yang Yu; Yawen Fan; Sihan Chen; Meiyi Mo; Shuo Yang; Yangyang Zhao; Zixu Zhang; Hongxian Han (Analytica Chimica Acta, 2026)

Constant frequency mapping mechanism for WECs and FPM-Net predictive control - Jianwei Wang; Xinyu Han; Weihang Zhang; Yuqing Wang; Minghua Yue; Shuo Sun; Tie Liu (Ocean Engineering, 2026)

Efficient hydrolysis of glycosides by Pichia kudriavzevii with high-activity β-glucosidase: a critical role in enhancing terpene aroma in beer - Lin Yuan; Xiaoping Hou; Yang He; Xiujuan Wan; Jiaxin Han; Wenqi Xu; Shuo Yu; Shuang Bi; Lijuan Ma; Lei Xing (Food Chemistry, 2026)

Waxy gene deficiency shapes the multi-level wheat starch structure and noodle quality - Fada Han; Shuo Zhang; Liqiang Song; Liang Chen; Maria Itria Ibba; Aimin Zhang; Boli Guo; Ming Li; Dongcheng Liu (Carbohydrate Polymers, 2026)

Exploratory observation of dietary exogenous bile acids on growth, hepatic glucose metabolism, intestinal and liver health, and fillet quality of Monopterus albus fed high-carbohydrate diets - Jiamin Li; Peng Fang; Ao Luo; Luyao Xu; Tianlun Luo; Junzhang Han; Tingting Li; Xiaoxuan Qi; Shuo Cheng; Huanhuan Huo; Mo Peng (Animal Feed Science and Technology, 2026)

Targeting programmed cell death: a novel therapeutic paradigm for cancer based on mode-of-death classification - Xi Qiao; Ting Ye; Tinggai Wu; Xu Han; Tiantian Sun; Haiqiang Wang; Junru Jia; Yuanyuan Dai; Ruohan Yun; Shuo Jiang; Yuming Qin; Zhenzhen Liu; et al. (Apoptosis, 2026)

Research on Non-destructive Detection of Chlorophyll in Zucchini Leaves Based on Machine Learning and Color Features - Xinyue Gou; Yuemei Sun; Xin Han; Yubin Lan; Huizheng Wang; Shuo Zhao; Jingbo Bai; Maochang Song (Agricultural Research, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Auxin is a signal for algal-bacterial inter-kingdom interactions in marine diatom algal blooms - Xinyang Li; Xueyu Cheng; Mengjie Wu; Shuo Han; Xiaobing Wen; Si Tang; Zhonghua Cai; Jin Zhou (Journal of Hazardous Materials, 2026)

A novel 3D-printed flexible electrode with rGO/MWCNTs ink for capsaicin detection in chilli peppers - Jiachen Zhao; Huilin Hu; Chao Wang; Yingting Li; Xueyu Jiang; Ming Zhang; Fangkai Han; Ning Yang; Xiaodan Liu; Jiahua Wang; Yingli Wang; Shuo Duan; et al. (Food Chemistry, 2026)

SWAT-UQ: A platform for uncertainty analysis, calibration and optimization of SWAT models - Mengtian Wu; Meihong Wu; Ruochen Sun; Xuan Huang; Shuo Yan; Jianjun Han; Qingyun Duan (Environmental Modelling & Software, 2026)

N-acetylcysteine-functionalized biodegradable polysaccharide hydrogel patches for the repair of acute liver injury - Shanshan Li; Lixin Xia; Shuo Wang; Ruibao Ju; Zi Han; Xiansen Lv; Baoqin Han; Jinhua Chi (Carbohydrate Polymers, 2026)

Nitrogen‐Driven Acidification and Microbial Shifts Contribute to a Breakdown in Carbon–Phosphorus Trade in the Rhizosphere - Shuo Sun; Ruzhen Wang; Jordi Sardans; Mengjiao Bi; Ying Zhang; Xinyu Fan; Xiaoyu Guan; Yong Jiang; Mingkai Jiang; Xingguo Han; Josep Peñuelas (Global Change Biology, 2026)
Anthropogenic nitrogen (N) deposition is reshaping terrestrial phosphorus (P) cycling. This effect is pronounced in the rhizosphere, where plants respond to P status by releasing root exudates. Yet it remains unclear whether these interactions drive P mobilization or immobilization. To capture both the chronic effects of N deposition and the transient effects of root exudates, we integrated a decade‐long N addition experiment (a single annual application of (NH 4 ) 2 SO 4 at 0, 2, and 5 g N m −2 year −1 ) with a 14‐day laboratory incubation. Specifically, rhizosphere and bulk soils from a Eurasian meadow steppe were amended with 13 C‐labeled low‐molecular‐weight organic acids (LMWOA; a single addition of acetic and succinic acids). Phosphorus transformation was quantified using sequential extraction and 31 P NMR, while underlying mechanisms were assessed via priming effects, phosphatase activity, and microbial functional genes. Nitrogen enrichment promoted the dissolution of mineral‐bound inorganic P (P i ) through acidification (pH drop > 1 unit), leading to the accumulation of secondary mineral P i and organic P (P o ). This was accompanied by reduced microbial phosphatase activity and lower abundances of the P‐cycling genes phoC and phoD . The above effects were stronger in the rhizosphere than in bulk soil. In the rhizosphere, LMWOA enhanced microbial P immobilization and P o accumulation, even as their positive priming effects accelerated soil organic carbon mineralization. These results were partly driven by the recruitment of key P‐cycling taxa such as Burkholderia and Rhodoplanes , suggesting a shift in carbon‐for‐P exchange between plants and microbes under N deposition. Collectively, our findings indicated that while N‐induced P solubilization may temporarily alleviate P limitation, synergy with increased LMWOA exudation promotes P o accumulation. Though P o can be labile compared to mineral‐bound forms, suppressed phosphatase activity likely constrains its mineralization. This inhibition potentially decelerates P cycling, thereby compromising the medium‐ to long‐term P supply within the Eurasian steppe.

AUV Path Planning Method for Underwater Moving Target Search Based on a Target-Position-Controlled Mutation Strategy Genetic Algorithm - Qiuying Wang; Shuo Zhang; Yunfeng Han (Journal of Marine Science and Engineering, 2026)
To accomplish underwater search missions of the target with stochastic motion, path planning is required prior to autonomous underwater vehicle (AUV) operations. Genetic algorithms (GAs) are a classical approach for target search path planning; however, when applied to moving underwater targets, they often rely on oversimplified motion models and lack flexible mutation direction control, resulting in suboptimal search paths and reduced detection performance. To address these limitations, this paper proposes a GA-based path planning method incorporating a target-position-controlled mutation strategy. First, a Markov process combined with a grid-based approach is used to model stochastic target motion and derive the spatial probability distribution of target positions. Second, based on the target distribution grid, the influence of random fluctuations on sonar signals is simulated to construct a probabilistic detection model. Finally, the target distribution and detection probability model are integrated into the proposed GA to generate an optimal AUV search path. Simulation results show that the proposed method effectively improves path planning for moving targets under stochastic conditions, increasing the target cumulative detection probability from 0.33 to 0.48.

Sustainable grouting materials derived entirely from solid wastes: An integrated analysis of performance, micro-mechanisms, and environmental benefits - Huairui Luo; Fenglei Han; Zonghan Liu; Ainiwaera Fuerhaiti; Shuo Wang; Ke Xu (Sustainable Chemistry and Pharmacy, 2026)

Seismic performance of trussed concrete-filled steel tubular (CFST) hybrid structures: Experiments - Zhan-Shuo Liang; Lin-Hai Han; Ming Xiao (Engineering Structures, 2026)

Intrusion of Marine-continental mixed aerosols disturb cloud properties - Shuo Wang; Wenqing Xu; Chang Liu; Jun Wang; Zhiming Yi; Liang Xu; Jing Han; Guangzhi Ren; Dianguo Zhang; Wenqing Wang; Weijun Li (Atmospheric Environment, 2026)

Ex vitro rooting of Spathiphyllum cannifolium in a microponic system: optimization of key physicochemical factors - Peng-Yu Zhang; Xue-Han Zong; Shuo Yu; Yin-Ji Jiang; Xin-Mei Jin; Song-Hao An; Mei-Lan Lian (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

Proteostasis Collapse Drives Effector Memory T Cells Re-expressing CD45RA (TEMRA) Generation in the Tumor Microenvironment - Linlin Li; Shuo Kan; Qiang Huang; Shiwen Wang; Yuchen Han; Liang Chen; Jun Jin (Phenomics, 2026)

Differential responses of soil microbial community structure and function to conventional and biodegradable microplastics - Yuhan Liu; Xue Bei; Chuanwei Zheng; Hong Lou; Huimei Tian; Wenjing Han; Wenxiao Sun; Songyan Jiao; Shuo Li; Bing Li; Lusheng Zhu; Zhongkun Du; et al. (Applied Soil Ecology, 2026)

A replication-defective bivalent adenovirus-vectored vaccine provides robust and durable protection against both canine distemper virus and canine parvovirus - Ying Hu; Xiaohu Han; Shuo Zhu; Yuan Zhang; Yifan Peng; Chengguang Zhang; Ming Zhou; Ling Zhao (Veterinary Microbiology, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Predicting macrolide resistance in pediatric Mycoplasma pneumoniae pneumonia: A machine learning modeling study - Shuo Yang; Xinying Liu; Huizhe Wang; Yaowei Han; Dan Sun; Huanmin Li; Liting Ma; Haokai Wang; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Numerical and experimental studies on the flow field of a semi-submersible aquaculture platform - Kai Wang; Yi-Han Wen; Jia-Ming Liu; Cheng Liang; Shuo Huang (Aquacultural Engineering, 2026)

Asymmetric Propagation of Hydraulic Fractures in Coal–Rock Composite Formations: Insights Based on Stress Sensitivity of Coal - Zhaolong Ge; Changzheng Lu; Qinglin Deng; Zhe Zhou; Shuo Dai; Jing Han; Jinming Cui (Rock Mechanics and Rock Engineering, 2026)

Continuous flow partial nitrification/anammox anaerobic-oxic-anoxic (PN/A-AOA) system for advanced nitrogen removal of low carbon to nitrogen ratio wastewater at different temperature: Long-term performance and mechanism - Yanchen Li; Wenyi Dong; Qi Han; Shuo Chen; Huaguang Liu; Hongjie Wang; Yongzhen Peng (Journal of Water Process Engineering, 2026)

Sustainable conversion of coal gasification fine slag into CaO-SiO2-H2O adsorbents for efficient removal and immobilization of Sr²⁺ in simulated seawater - Chunbin Guo; Yueci Liu; Jianjun Guo; Xuefeng Han; Shuo Liang; Zhongrui Shi; Genhua Luo; Tiantian Han; Jingjing Zou (Journal of Environmental Chemical Engineering, 2026)

Dissolved iron concentrations in the upper 500 m waters of the eastern Indian ocean - Han Su; Jie Jin; Shuo Jiang; Wei Zheng; Zheng Bo Liu; Yan Chang; Xunchi Zhu; Jing Zhang (Deep Sea Research Part I: Oceanographic Research Papers, 2026)

A novel pathologic scoring system for predicting postoperative recurrence in BCLC stage 0-A hepatocellular carcinoma patients: a nationwide multicenter study - Feng Xia; Jing Yan; Xulin Liu; Zhao Huang; Zhancheng Qiu; Qiao Zhang; Zhenheng Wu; Zhiyuan Huang; Renjie Wei; Li Lin; Liping Liu; Shuangqin Han; et al. (Science China Life Sciences, 2026)

Monocyte-mediated mechanisms in idiopathic pulmonary fibrosis: opportunities for early intervention - Zhiguo Mao; Ying Liu; Chengfu Han; Xingyi Yang; Xiangke Lin; Shuo Tian; Mingsan Miao (Apoptosis, 2026)

Comparison of apple fruit waxes and quality when stored at 25 ℃ under different humidity conditions - Kui-Tao Zhang; Min-Min Zhou; Wen-Shuo Xue; Zi-Heng Wang; Wen-Teng You; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Postharvest Biology and Technology, 2026)

Starch/polyvinyl alcohol based smart packaging reinforced with recycled pitaya peel-derived anthocyanins for dual-function pork freshness monitoring and shelf-life extension - Lili Ma; Wenyu Han; Yurou Jiang; Zhenquan Yang; Dan Xiong; Shuo Wang; Wenyuan Zhou; Xin-an Jiao; Lei Yuan (Meat Science, 2026)

Biodegradable polyester-polycarbonate copolymers from thiophenedicarboxylic acid with high thermal, mechanical and gas barrier properties - Xiaoqin Zhang; Shuo Han; Bin Fang; Jin Zhu; Jinggang Wang (Chemical Engineering Journal, 2026)

A bioinspired high-sensitivity and wide-range ionic capacitive pressure sensor for remote motion control and robotic object recognition - Shuo Zhang; Liuqi Ji; Siyuan Wang; Yunduo Yi; Dakai Wang; Changchao Zhang; Bo Li; Shichao Niu; Junqiu Zhang; Zhiwu Han; Luquan Ren (Chemical Engineering Journal, 2026)

STAT3 Signaling Mediates Agomelatine Restoration of Prefrontal Cortex Synaptic Plasticity in Chronic Social Defeat Stress Mice - Chi-Wei Lee; Han-Fang Wu; Hsin-Ju Yen; Lun-De Liao; Wei-Chang Mao; Hsun-Shuo Chang; Yih-Fung Chen; Chia-Hsien Lin; Cheng-Ta Li; Hui-Ching Lin (Molecular Neurobiology, 2026)
Major depressive disorder (MDD) is a major public health issue worldwide. It not only causes an increased socio-economic burden, but also negatively affects personal lives. It has been shown that depression leads to impairments in synaptic plasticity, such as impaired long-term potentiation (LTP) in the prefrontal cortex (PFC). A recent study reported that administration of agomelatine, a melatonin receptor agonist and 5-hydroxytryptamine (5-HT) 2C antagonist, which may be involved in synaptic functions, for 1 week has a rapid antidepressive effect. Moreover, the mechanism of Glycogen synthase kinase 3β (GSK3β), regulated by signal transducer and activator of transcription 3 (STAT3), may play an important role in the synapse-related pathological mechanisms of depression. Hence, we used chronic social defeat stress (CSDS) as an animal model of depression, to investigate whether synaptic plasticity impairment in depression, improved by agomelatine, is mediated through the STAT3 mechanism. The results showed that depressive-like behaviors were reversed after 1 week of agomelatine treatment. Moreover, the impairment of LTP and alteration of spine density were reversed by agomelatine in the PFC. We further applied AG490, an inhibitor of STAT3, to demonstrate that the therapeutic mechanism of agomelatine improves synaptic plasticity through STAT3-regulated phosphorylation of GSK3β. Taken together, these results demonstrated that STAT3-regulated downstream molecules are potential therapeutic targets for the rapid action of antidepressants.

Sensitive MicroRNA detection via single nanoparticle collision electrochemistry using DNA-functionalized silver nanoparticles - Xiao-Han Yuan; Shuo Zhang; Jian-Hua Zhang; Xin-Yue Meng; Dian-Mei Song; Wen-Min Zhang (Analytica Chimica Acta, 2026)

Bee venom alleviates isoproterenol-induced cardiac hypertrophy via JAK2/NF-κB signaling cascade - Peiying Shi; Shuo Han; Yang Sun; Mengmeng Li; Xueling Xu (Tissue and Cell, 2025)

PromptMID: Modal invariant descriptors based on diffusion and vision foundation models for optical-SAR image matching - Han Nie; Bin Luo; Jun Liu; Zhitao Fu; Huan Zhou; Shuo Zhang; Weixing Liu (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Production of cellulose nanocrystals from waste Phellinus igniarius substrate by enzymatic hydrolysis-centrifugal fractionation method: Construction of a bioactive substance delivery system - Shuo Zhang; Shuang Guo; Jiayu Han; Zhaolian Han; Hailing Yu; Xue Zhang; Ningcan Ma; Zhiqiang Cheng (Food Research International, 2025)

Assembling L-malic acid and Co-MOF in ultrasonically synthesized pectin/gelatin films: A versatile food preservation composite film - Xu Han; Wen-Shuo Xue; Shang Wu; Qi Zhang; Wei-Teng You; Zi-heng Wang; Han Jiang; Ya-Li Zhang; Yuan-Yuan Li (Food Chemistry, 2025)

Scalable production of Actinidia arguta adventitious roots in air-lift bioreactors and their antibacterial efficacy against Staphylococcus aureus - Wen Jiang; Xue-Han Zong; Song-Hao An; Jing-Run Xiu; Shuo Yu; Ke-Xin Zhang; Yue-Jun Hao; Mei-Yu Jin (In Vitro Cellular & Developmental Biology - Plant, 2025)

Effect of in-tire backfill material weights on the seismic performance of geogrid-wrapped tire-faced retaining walls - Bin Ma; Liyan Wang; Shuo Wang; Xiang Hu; Han Wu; Binghui Wang (Soil Dynamics and Earthquake Engineering, 2025)

Distinct adaptation strategies and functional potentials of abundant and rare prokaryotes across seasonal dynamics and long-term eutrophication in Xiangshan Bay - Hongjing Luo; Kunpeng Xie; Fengyuan Zhang; Zhen Bao; Shuo Ren; Qingxi Han; Dandi Hou; Demin Zhang; Zheng Gong; Huajun Zhang (Marine Environmental Research, 2025)

Fabrication of surface molecularly imprinted electrochemical sensor based on V2CTx MXene heterogeneous functionalized Au-PtRu nanoalloy for the sensitive detection of chlortetracycline in food - Bo Zhang; Yanrong Han; Yanrong Chen; Chenyu Wang; Guozhen Fang; Shuo Wang (Food Chemistry, 2025)

Photodynamic bacterial inactivation by a ferulic acid-based hydrogen-bonded photoactive edible coating for fresh fruit preservation - Shuo Shi; Xi Lan; Xiyan Ding; Liping Wang; Ximei Han; Jing Sun; Jianlong Wang; Jinyou Duan (Food Chemistry, 2025)

Toxic risk assessment of multi-endpoint toxicity and toxicity transformation mechanisms during UV-combined advanced treatments in wastewater treatment plants: Development of effect-based trigger values, in vitro bioassays, and FT-ICR MS analysis - Shuo Zhang; Kongrui Zhu; Kaifeng Rao; Yingnan Han; Jing-Long Han; Mei Ma; Aijie Wang; Jifang Zhang; Zhihang Yuan (Environmental Pollution, 2025)

Optimizing lithium extraction from brines using fluoride-doped lithium titanate in hybrid capacitive deionization - Jiahui Zhang; Wen Xi; Jianing Hu; Qingqing Han; Youfang Zhang; Shuo Huang; Rui Wang; Huanwen Wang; Yansheng Gong; Jun Jin (Desalination, 2025)

Acidification boosts the photodynamic activity of anthocyanidin for enhanced sterilization - Zhenqing Guo; Yajie Wang; Xinqi Wang; Ting Du; Kaiyuan Su; Lin Yang; Yaru Han; Shuo Shi; Jianlong Wang; Wentao Zhang (Chemical Engineering Journal, 2025)

Boosting power output of NH3BH3 fuel cell by modulating H* and OH− adsorption via Cu@Pd core-shell structured nanowire arrays - Shuo Bi; Libo Zhu; Han Tian; Fantao Kong; Xu Yu; Qin Li; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Corrigendum to “Multichannel nerve conduit based on chitosan derivates for peripheral nerve regeneration and Schwann cell survival” [Carbohydrate Polymers 301 (2023) 120327] - Zhiwen Jiang; Yijie Zhang; Yanting Wang; Shuo Wang; Jing Chang; Wanshun Liu; Baoqin Han (Carbohydrate Polymers, 2025)

Unveiling dynamics of microbial communities, species interactions, and ecological assembly during low-temperature-induced sludge bulking in full-scale wastewater treatment systems - Han-Jun Sun; Xian Zhao; Jie Ding; Yu-Qian Wang; Wen-Shuo Wang; Zhi-Hua Feng; Sha Zhao; Liang Wang; Nan-Qi Ren; Shan-Shan Yang (Bioresource Technology, 2025)

Z-scheme Cu2O/g-C3N4/Ag heterostructures: A novel approach for simultaneous water pollutant removal and real-time SERS monitoring - Kaiyue Li; Wenhui Li; Ping Huang; Yuquan Zhuo; Ziwen Yang; Bo Wang; Runru Liu; Bing Liu; Enzhu Hou; Shuo Yang; Donglai Han (Journal of Environmental Chemical Engineering, 2025)

Nitrogen addition decouples the microbial necro-mass from soil organic carbon formation in a temperate grassland - Huanhuan Cheng; Yingbin Li; Shuo Li; Tianran Sun; Guoxiang Niu; Qi Li; Junjie Yang; Yanxia Ma; Yingzhi Gao; Qiang Yu; Haitao Zhao; Qiushi Ning; et al. (Journal of Environmental Sciences, 2025)

Three-dimensional reconstruction of shallow seabed topographic surface based on fusion of side-scan sonar and echo sounding data - Chunqing Ran; Luotao Zhang; Shuo Han; Xiaobo Zhang; Shengli Wang; Xinghua Zhou (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Variations in quality attributes of cow and goat milk subjected to microwave and high-pressure treatments over a two-week storage period - Nina Ding; Qiyue Sun; Zhongna Yu; Qijing Du; Rongbo Fan; Guangxu Ren; Liangliang You; Shuo Feng; Yongxin Yang; Rongwei Han (Innovative Food Science & Emerging Technologies, 2025)

Sensitive dual detection of N-nitrosodiphenylamine and N-nitrosodiethylamine using a PtNPs-enhanced MWCNTs/Fe-porphyrinic MOF nanocomposite-based electrochemical sensor - Jiachen Zhao; Yue Zou; Junlan Yu; Chao Wang; Yili Hu; Fangkai Han; Ning Yang; Fuwei Pi; Ming Zhang; Xiaodan Liu; Jiahua Wang; Huang Dai; et al. (Food Chemistry, 2025)

Photoelectrochemical sensor incorporating AgNPs-integrated BiOBr/Ti3C2 layed composites for the efficient detection of bisphenol A detection in water and milk samples - Mingfei Pan; Mengjiao Xie; Lu Han; Chan Lu; Jing Cao; Wenjie Chen; Shuo Wang (Food Chemistry, 2025)

Subsurface structure of a buried Eratosthenian crater on the far-side of the Moon - Ling Zhang; Chunyang Zhao; Xintong Dong; Shaoping Lu; Yi Xu; Yuqi Qian; Shuo Han; Zhijun Huo; Rui Gao (Earth and Planetary Science Letters, 2025)

Dopant alliance: K/Cu cooperative bonds lock structural stability in P2-type sodium cathodes - Yu Duan; Jia-xuan He; Zi-han Ma; Shu-wen Chen; Ying-ying Huang; Shuo Bao; Jin-lin Lu (Chemical Engineering Journal, 2025)

Causal Matrix Long Short-Term Memory Network for Interpretable Significant Wave Height Forecasting - Mingshen Xie; Wenjin Sun; Ying Han; Shuo Ren; Chunhui Li; Jinlin Ji; Yang Yu; Shuyi Zhou; Changming Dong (Journal of Marine Science and Engineering, 2025)
This study proposes a novel causality-structured matrix long short-term memory (C-mLSTM) model for significant wave height (SWH) forecasting. The framework incorporates a two-stage causal feature selection methodology using cointegration testing and Granger causality testing to identify long-term stable causal relationships among variables. These relationships are embedded within the C-mLSTM architecture, enabling the model to effectively capture both temporal dependencies and causal information within the data. Furthermore, the model integrates Bayesian optimization (BO) and twin delayed deep deterministic policy gradient (TD3) algorithms for synergistic optimization. This combined TD3-BO approach achieves an 11.11% improvement in the mean absolute percentage error (MAPE) on average compared to the base model without optimization. For 1–24 h SWH forecasts, the proposed TD3-BO-C-mLSTM outperforms the benchmark models TD3-BO-LSTM and TD3-BO-mLSTM in prediction accuracy. Finally, a Shapley additive explanations (SHAP) analysis was conducted on the input features of the BO-C-mLSTM model, which reveals interpretability patterns consistent with the two-stage causal feature selection methodology. This research demonstrates that integrating causal modeling with optimization strategies significantly enhances time-series forecasting performance.

Efficient extraction of pectin from spaghetti squash (Cucurbita pepo L. subsp. pepo) peel by electron beam irradiation combined with ultrasound: Structural characterization and functional properties - Shuo Wang; Hui Han; Xinying Zhang; Xiaoyun Mao; Yali Li; Zhou Si; Niuniu Song; Yamei Ren (Food Chemistry, 2025)

Bridge influence surface identification using a physical informed neural network and its application on load transverse localisation - Lu Deng; Dayong Han; Longwei Zhang; Shuo Wang (Engineering Structures, 2025)

Thermal regulation of nitrogen vacancies in double metal-supported nanofibers through persulfates activation for enhanced 1O2 generation and electron transfer in antibiotic removal - Heshan Zheng; Han Lu; Shuo Li; Xu Dong; Yoong Kit Leong; Xiaoliu Huangfu; Tomasz Gierczak; Bartlomiej Witkowski; Jo-Shu Chang (Chemical Engineering Journal, 2025)

Corrigendum to “Effects of carboxymethyl chitosan oligosaccharide on regulating immunologic function and inhibiting tumor growth” [Carbohydrate Polymers 250 (2020) 116994] - Zhiwen Jiang; Shuning Wang; Jun Hou; Jinhua Chi; Shuo Wang; Kai Shao; Wanshun Liu; Rongju Sun; Baoqin Han (Carbohydrate Polymers, 2025)

A stepwise-clustered concurrent extreme analysis for concurrent drought-heatwave events: a case study of North China - Shuo Han; Guohe Huang; Xiong Zhou; Shuguang Wang; Yongping Li; Bizheng Yu; Wenshu Kuang (Climatic Change, 2025)

Accelerating enrichment of ARGs and MGEs with increasing ammonium removal during partial nitrification treating high-strength ammonia wastewater - Heng Yu; Weiyi Jia; Yuqiu Luo; Rong Zhang; Junkai Zhao; Cong Lu; Yue Dong; Shuo han; Bing Li; Chengtun Qu (Environmental Research, 2025)

Energy-dissipating binder for self-healing sulfurized polyacrylonitrile electrode for rechargeable lithium batteries - Qihang Wang; Lizhi Xiang; Huichao Lu; Shuo Liu; Chenran Hao; Jiqiong Liu; Jing Han; Jun Yang; Yanna NuLi; Jiulin Wang (Chemical Engineering Journal, 2025)

Experimental Investigation of Grout Flow Behaviour Through Rough Parallel Multi-Fractures - Yuhao Jin; Lijun Han; Shuo Yang; Hui Guo; Shanjie Su; Lanying Huang; Deyuan Zong; Peitao Qiu; Kun Hu (Rock Mechanics and Rock Engineering, 2025)

Dual-stage matrix elimination-ICP-MS methodology for REEs profiling in barite-associated ores - Xue-lin Dong; Jun-han Liu; Zheng-xun Jia; Shao-zhan Tang; Shuo-yun Tong; Yu-xiang Xiong; Lei Ouyang (Analytica Chimica Acta, 2025)

Coupling soil bacterial and fungal community traits to multifunctionality in grassland ecosystem - Chenxiao Ding; Yaowei Liu; Marcela Hernández; Han Sun; Shuo Jiao; Hong Pan; Tida Ge; Kankan Zhao; Qichun Zhang; Jianming Xu; Yong Li (Agriculture, Ecosystems & Environment, 2025)

Advancements in the investigation of the mechanisms underlying cognitive aging - Honglu Zou; Shuo Zhang; Xinxin Cui; Hongyan Xu; Zhangying Zhou; Danmeng Cheng; Yanan Han; Youcai Tang; Anqin Dong; Xianwen Dong (Biogerontology, 2025)

Mechanism study and thermodynamic analysis of iron recovery from Sulfuric acid slag by suspension magnetization roasting and magnetic separation - Wenbo Li; Maoyuan Wang; Shuo Wang; Yuexin Han; Zhidong Tang; Yahui Zhang (Process Safety and Environmental Protection, 2025)

Metabolome insights into nutrients and glucosinolates in broccoli and lacinato kale - Wenzheng Gao; Shangxiang Lai; Guangmin Liu; Yumei Liu; Fengqing Han; Shuo Zhang; Hongju He; Zhansheng Li (Food Chemistry, 2025)

Experimental testing and machine learning to predict the load-slip behavior of stud connectors in steel-UHPC composite structures - Yong-jian Zhou; Xia Yang; Wu-wu Zou; Cheng-shuo Han (Engineering Structures, 2025)

Performance of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to eccentric compression - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2025)

The role of LNK in mitigating hypertension: inhibition of vascular smooth muscle proliferation and JAK-STAT pathway - Xinxin Han; Shuo Wei; Ali Ahmad; Yibo Cao; Caihong Zhao; Mengyang Yan; Jing Zhao; Xingmei Deng; Hongsu He; Zhihua Sun (Molecular and Cellular Biochemistry, 2025)

Structure and Function Features of Abundant and Rare Prokaryotic Communities Along Nearshore to Offshore Transitions - Mengjie Wu; Tingrui Zhang; Shuo Han; Shengxin Huan; Yuelu Jiang; Yong Wang; Zhonghua Cai; Jin Zhou (Environmental Microbiology, 2025)
Abundant and rare taxa are crucial members of the marine microbial community. However, their biodiversity, assembly mechanisms, functional characteristics and ecological response strategies remain poorly understood. In this study, 16S rRNA and metagenomic sequencing were carried out to reveal the structural and functional features of abundant and rare taxa across the transition from nearshore to offshore. The results showed that the biodiversity of both abundant and rare taxa decreased with increasing distance from shore, with rare taxa exhibiting relatively higher diversity indices than abundant ones. Neutral model analysis revealed that the assembly process gradually changed from deterministic to stochastic from nearshore to offshore among abundant taxa. In contrast, among rare taxa, a stochastic process dominated nearshore, whereas a deterministic process was predominant in the offshore environment. Meanwhile, the proportion of variance that could be explained by environmental factors was relatively higher among abundant communities than among rare ones. A co‐occurrence network analysis indicated that rare communities displayed greater complexity and a higher degree of modularity than abundant communities. Functionally, abundant communities tended to favour an r‐strategy, whereas rare communities leaned towards a K‐strategy. Our results strengthen the understanding of the ecological mechanisms controlling microbial community patterns along coastal‐to‐open water transitions.

Response of diatoms to environmental changes in the Porphyra cultivation system in Haizhou Bay using GBT model and GAM - Shuo Chen; Haibin Han; Jinchen Yu; Tao Sun; Jin Zhou (Marine Pollution Bulletin, 2025)

Phytolith formation and its contribution to soil organic carbon sequestration in an Inner Mongolia grassland under long-term nitrogen deposition - Shuo Li; Liangchao Jiang; Guojiao Yang; Xingguo Han; Dongmei Jie; Niankang Chen; Haiyang Zhang (Journal of Environmental Management, 2025)

Interspecies interactions promote dual-species biofilm formation by Lactiplantibacillus plantarum and Limosilactobacillus fermentum: Phenotypic and metabolomic insights - Bingxin Zhang; Yuxin Sun; Wenyu Han; Wenwen Ge; Zhenbo Xu; Shuo Wang; Zhenquan Yang; Lei Yuan (Food Research International, 2025)

Correction to: Comparison of Long‑Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2025)

Developing a drought-heatwave cluster projection (DHCP) approach for water shortage areas: A case study in Northwest China - Yingxia Tang; Guohe Huang; Wenshu Kuang; Shuo Han; Shuguang Wang; Yongping Li; Bizheng Yu (Theoretical and Applied Climatology, 2025)

Clinical characteristics and associated factors of macrolide-resistant mycoplasma pneumoniae pneumonia in children: a systematic review and meta-analysis - Shuo Yang; Xinying Liu; Yaowei Han; Huizhe Wang; Yunzheng Mei; Haokai Wang; Na Zhang; Yingying Peng; Xinmin Li (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Intricate relationship among major heat-induced harmful by-products and modulating role of lipid and protein oxidation in seafood: A comprehensive review - Huaixu Wang; Baoping Shi; Zening Zhang; Lingling Zhao; Haixia Xiong; Shuo Han; Qi Wang; Ka-Wing Cheng (Food Research International, 2025)

Elucidation of potential lipid precursors and formation pathways for the warmed-over flavor (WOF) in precooked Chinese stewed beef through lipid oxidation mechanisms - Junmei Liu; Feng Huang; Dong Han; Ying Xu; Shuo Shen; Yanlu Luan; Ping Yang; Chunhui Zhang; Christophe Blecker (Food Chemistry, 2025)

Rapid and interference-resistant colorimetric detection of viable Staphylococcus aureus in food using a broad host range phage SapYZU04 and MnFeO nanozyme - Aiping Deng; Xuan Li; Xiaoxing Fan; Yajie Li; Yelin Han; Tianzhu Guan; Shuo Wang; Guoqiang Zhu; Zhenquan Yang; Wenyuan Zhou (Food Control, 2025)

Evolutionary and functional insights into Fibrinogen-related protein (FREP) dynamics in sea cucumbers - Shuo Li; Chen Li; Shenglei Han; Kaiyu Chen; Weijing Li; Shuhong Jiang; Duan Liao; Changwei Shao; Chenghua Li (Fish & Shellfish Immunology, 2025)

A novel antioxidant peptide from soybean meal alleviates H2O2-induced oxidative damage via the Keap1-Nrf2-HO-1 pathway - Yiding Yu; Sitong Ma; Yuxi Han; Shuo Zhang; Meng Yang; Zhiyang Du; Zhipeng Yu; Chunmei Liu (Food Research International, 2025)

Self-powered multisensory neuromorphic device with auditory and rotational perception integration inspired by the labyrinth of the inner ear - Feiyu Wang; Jia-Han Zhang; Shuo Ke; Jiean Li; Fengchang Huang; Wen Cheng; Yi Shi; Lijia Pan (Chemical Engineering Journal, 2025)

The depth-dependent study of microalgae growth under continuous culture conditions at different depths was considered - Fuwang Wu; Shuo Yuan; Wenshang Ma; Wenbin Lei; Yubo Han; Yudong Peng (Biomass and Bioenergy, 2025)

FAM64A regulates the malignant phenotype and tumor microenvironment of non-small cell lung cancer by activating the JAK/STAT3/PDL1 axis - Shuo Shi; Jiahui Han; Qianbiao Wu; Haoqiu Zhong; Binfeng Lei; Yibo Yan (Journal of Molecular Histology, 2025)

Spatial Distribution and Quantitative Source Identification of Heavy Metals in Soil of a Typical Industrial Park, East of China - Shiyu Wang; Junnan Zhang; Jingyuan Sun; Fada Zhou; Pingping Wang; Zhirui Qin; Yue Zhao; Shuo Wang; Ziyu Han; Wentao Jiao (Bulletin of Environmental Contamination and Toxicology, 2025)

A New Screening Strategy for Flavonoid Components to Obtain a Satisfactory Co-Amorphous System with Piperine - Jiawei Han; Wen Sun; Yongxu Yao; Shuo Li; Zhimin Yue; Weitao Fang; Xiaoqian Liu; Jue Wang; Jiaxin Chen (AAPS PharmSciTech, 2025)

Broad-spectrum anti-inflammatory and antioxidant therapy of inflammatory-storm actuated diseases via programmable self-derived cryo-dead neutrophils - Bin Li; Qiuxia Gao; Yunxia Wu; Hongyi Lei; Shengchao Ma; Wei Wang; Hang Sun; Weifeng Ma; Judun Zheng; Chenchen Yuan; Yunlong Zhang; Yue Jia; et al. (Chemical Engineering Journal, 2025)

Cyclic-di-GMP modulates lapA-mediated biofilm formation of Hafnia paralvei to enhance its intestinal colonization and injury - Mengyuan Qin; Wenfang Niu; Chao Gao; Yuqi Wang; Shuo Han; Xiaohua Xia; Yi Li (Aquaculture, 2025)

Oily-bubble and its typical applications in enhancing the separation and mass transfer processes: A review and perspectives - Tianze Chen; Shengpeng Su; Shuo Chen; Yizhuang Wang; Yanfang Huang; Bingbing Liu; Hu Sun; Shuzhen Yang; Guihong Han (Minerals Engineering, 2025)

A novel 0D/2D heterojunction Bi2Sn2O7/BiOCOOH with BiOCOOH nanosheets as support for the boosted photodegradation of tetracycline: The role of BiOCOOH in the photogenerated electron transfer - Shuo Han; Fangyan Chen; Yubin Tang; Wenqian Sun; Yanhua Song; Kaiwen Zhang; Na Li (Journal of Environmental Chemical Engineering, 2025)

Evaluating hydraulic permeability of hydrate-bearing porous media based on broadband electrical parameters: A numerical study - Lanchang Xing; Shuo Wang; Xiaofei Wu; Liyun Lao; Seyed Milad Salehi; Wei Wei; Weifeng Han; Donghui Xing; Xinmin Ge (Gas Science and Engineering, 2025)

Cation-doping tuned flower-like Co-based spinel structure for methane combustion: Structure-effect and reaction pathway confirmation - Xi Zhang; Shuo Yao; Mingjuan Han; Nengjie Feng; Hui Wan; Guofeng Guan (Fuel, 2025)

Effect of chitosan and its derivatives on food processing properties of potato starch gel: Based on molecular interactions - Xinying Zhang; Xiaoyun Mao; Hui Han; Shuo Wang; Xiaoqing Lei; Yali Li; Yamei Ren (Food Hydrocolloids, 2025)

Performance and calculation of trussed concrete-filled steel tubular (CFST) hybrid structures subjected to bending - Zhan-Shuo Liang; Lin-Hai Han; Pu Wang (Engineering Structures, 2025)

Observed dissolved gallium in the tropical and subtropical waters in the Western Pacific Ocean - Zheng Bo Liu; Jing Zhang; Shuo Jiang; Han Su; Jingling Ren; Hang Zhang; Shijian Hu (Chemical Geology, 2025)

Screening of Genes Associated with Immune Infiltration of Discoid Lupus Erythematosus Based on Weighted Gene Co-expression Network Analysis - Yuru Han; Shuang Liu; Shuo Shi; Yongyong Shu; Changlian Lu; Xuefeng Gu (Biochemical Genetics, 2025)

Activation of the De Novo Serine Synthesis Pathway and Disruption of Insulin Signaling Induced by Supplemental SeMet in Vitro - Shuo Zhan; Jiaqiang Huang; Yiqun Liu; Feng Han; Jianrong Wang; Qin Wang; Zhenwu Huang (Biological Trace Element Research, 2025)

Watt-level power density of direct borohydride fuel cells enabled by electrode local-environment and mass transport regulations - Libo Zhu; Tiantian Wu; Shuo Bi; Changchun Ke; Chang Chen; Han Tian; Fantao Kong; Xiangzhi Cui; Jianlin Shi (Chemical Engineering Journal, 2025)

Achieving efficient anammox contribution and the enrichment of functional bacteria in partial denitrification/anammox system: Performance, microbial evolution and correlation analysis - Zilong Hou; Wenyi Dong; Yanchen Li; Shuo Chen; Huaguang Liu; Qi Han; Zilong Zhao; Jie Liu; Liang Zhang; Hongjie Wang; Yongzhen Peng (Bioresource Technology, 2025)

Design and green synthesis of asymmetric 3,4,5-trimethoxyphenyl-inspired 1,5-diaryl-1,4-pentadien-3-ones as potent anti-gastric cancer agents through ROS and JNK-triggered apoptosis - Jianzhang Wu; Song Yao; Danjie Wang; Mengke Han; Yingwen Liu; Shuo Ren; Liping Chen; Min Zhu; Qian Li; Tao Wu; Yujia Li; Jiabing Wang; et al. (Sustainable Chemistry and Pharmacy, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Remediation of atrazine contaminated soil with the help of hydrothermal carbon/diatomite composite inoculated with degrading microorganisms - Tong Zhang; Hailing Yu; Zhaolian Han; Shuo Zhang; Jingjing Zhang; Shuang Xu; Zhihui Dong; Zhiqiang Cheng (Journal of Environmental Chemical Engineering, 2024)

Electrostatic self-assembly of hydrotalcite-based g-C3N4 composites for adsorption and photocatalytic degradation of aqueous norfloxacin - Xiaodong Yang; Minghui Li; Zhiyong Hou; Xuefei Yang; Yuanxia Guo; Shuaiqi Luo; Jin Zhao; Kai Wang; Pengkai Sun; Qiang Yang; Rui Chen; Shuo Yang; et al. (Journal of Environmental Chemical Engineering, 2024)

Multifunctional pectin-based films containing schiff base triggered by pH microenvironment for freshness monitoring and preservation of fresh-cut papayas - Ping Han; Jiayang Sun; Shuo Mao; Fangyu Li; Xiaoxia Yan; Tiehua Zhang; Chengwen Lu (Food Hydrocolloids, 2024)

A comprehensive approach for quantifying source-specific ecological and health risks of potentially toxic elements in agricultural soil - Li-Mei Cai; Ke Quan; Han-Hui Wen; Jie Luo; Shuo Wang; Lai-Guo Chen; He Song; Ao Wang (Environmental Research, 2024)

Crocin-1 laden thermosensitive chitosan-based hydrogel with smart anti-inflammatory performance for severe full-thickness burn wound therapeutics - Xiansen Lv; Hui Li; Ya Chen; Yanting Wang; Jinhua Chi; Shuo Wang; Yan Yang; Baoqin Han; Zhiwen Jiang (Carbohydrate Polymers, 2024)

Comparison of Long-Term Outcomes in Ruptured Diffuse Brain Arteriovenous Malformations Between Interventional Therapy and Conservative Management - Changyu Lu; Heze Han; Li Ma; Ruinan Li; Zhipeng Li; Haibin Zhang; Kexin Yuan; Yukun Zhang; Anqi Li; Ke Wang; Yang Zhao; Weitao Jin; et al. (Translational Stroke Research, 2024)

Roseomonas populi sp. nov., an acetate-degrading bacteria isolated from the stem of Populus tomentosa - Yao Cheng; Wen Zhu; Shuo Han; Jingjing Yang; Guanqi Wu; Guozhu Zhao; Xiangwei He (Antonie van Leeuwenhoek, 2024)

Bee venom prompts the inhibition of gefitinib on proliferation, migration, and invasion of non-small cell lung cancer cells via EGFR-mediated autophagy - Shihui Xie; Shuo Han; Jietao Gong; Zhiyuan Feng; Yang Sun; Hong Yao; Peiying Shi (Toxicon, 2024)

Effects of saccharide type and extended heating on the Maillard reaction and physicochemical properties of high-solid gelatin gels - Ruican Wang; Xinyu Zhai; Richard W. Hartel; Yawei Chang; Wenwen Pang; Wen Han; Huan Lv; Shuo Wang (Food Chemistry, 2024)

Microplastics colonized by Hafnia paralvei through biofilm formation regulated by c-di-GMP and cAMP promote its spread in water - Yi Li; Mengyuan Qin; Wenfang Niu; Chao Gao; Yuqi Wang; Shuo Han; Xiaohua Xia (Aquatic Toxicology, 2024)

Mercaptopropionic acid-capped CdZnTe Quantum dots as Fluorescence Probe for Sensitive Detection of Cr(III) ions - Min Wu; Dongmei Zeng; Shuo Han; Minmin Zou; Ting Zhang; You Zhang (Journal of Fluorescence, 2024)

Development of a novel variable-curvature soft gripper used for orientating broccoli in the trimming line - Yongkai Ye; Chaoyue Han; Shuo Kang; Jianzhuang Zhao; Rob B.N. Scharff; Jun Wang; Dongdong Du (Computers and Electronics in Agriculture, 2024)

Oxidation and spontaneous combustion characteristics of particulate coal under stress–heat–gas interactions - Jiangkun Chao; Shuo Wei; Ling Shen; Xuefeng Han; Rongkun Pan; Jie Li; Shuang Liu; Daimin Hu (Science of The Total Environment, 2024)

Vortex/wake-induced vibrations characteristics of tandem composite risers at moderate Reynolds number - Li Zhu; Xiaohui Ren; Zhen Liu; Yongbo Zhang; Peng Li; Xinyu Han; Shuo Dong; Yeshuo Wang (Ocean Engineering, 2024)

Catalytic upgrading of biomass pyrolysis volatiles over Y zeolites modified with different metal oxides - Ji Xu; Yuxin Wen; Dekang Li; Shuo Zhang; Zhen Han; Haoquan Hu; Lijun Jin (Fuel, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Visible light-responsive vitamin B2 functionalized ZnO with dual-mechanism bactericidal effects for perishable agrofood preservation - Jianxing Feng; Zhenqing Guo; Runli Li; Chaoqun Zhang; Ting Du; Xiang Li; Xuewei Yang; Junchen Zhuo; Yanmin Liang; Yaru Han; Jianlong Wang; Shuo Shi; et al. (Chemical Engineering Journal, 2024)

Construction of Covalent organic frameworks with bex topology for efficient photocatalytic hydrogen production - Lin Wang; Changzhi Han; Jingwen Pan; Shuo Li; Jia-Xing Jiang; Fengyun Guo; Shiyong Gao; Dongbo Wang; Yong Zhang (Chemical Engineering Journal, 2024)

Research on Hydrodynamics of Trans-Media Vehicles Considering Underwater Time-Varying Attitudes - Shuo Liu; Chihao Du; Yijie Han; Yu Zhang; Wanglin Lin; Yong Cai; Tao Wang (Journal of Marine Science and Engineering, 2024)
A trans-media vehicle is a new type of equipment that can adapt to two environments, water and air, to maintain optimal hydrodynamic and aerodynamic performance. However, no matter what kind of trans-media vehicle, its dynamics are much more complicated when traversing the interface of the medium, as the parameters are time-varying due to the change in ambient medium and vehicle attitudes. In order to improve the stability and performance of the trans-media vehicle in complex environments, an accurate mathematical model is established to characterize the dynamics of the trans-media vehicle in this process in this study. The time-varying hydrodynamic coefficients with different attitudes or depths are obtained using computational fluid dynamics software. The mathematical model is solved iteratively using a Runge–Kutta solver to calculate the dynamic response. A prototype of trans-media vehicle is fabricated, and motion experiments are performed in the pool. The experimental results confirm the effectiveness of the established model and lay the foundation for further controller design, providing a reference for the dynamic modeling of other similar equipment operating in complex environments. The primary novelty of this study lies in the fact that the established dynamic model considers the complex interaction between the attitude of the trans-media vehicle and the inherent different properties of water and air and utilizes computational fluid dynamics software to accurately obtain time-varying coefficients under different attitudes and depths. This approach not only recognizes the criticality of orientation-dependent hydrodynamic coefficients but also incorporates their temporal variations, which were often overlooked in previous studies.

Dissolved trace elements in the Ganges–Brahmaputra–Meghna River Basin: A new approach for estimating trace element flux inputs from rivers into the world's oceans - Han Su; Md. Jaker Hossain; Sheikh Aftab Uddin; Shan Jiang; Yan Chang; Shuo Jiang; Xin Shi; Zheng Bo Liu; Lijun He; Jing Zhang (Journal of Environmental Management, 2024)

Insight into the promoted recrystallization and water distribution of bread by removing starch granule - surface and - associated proteins during storage - Han Tao; Li-Jiao Huang; Shuo-qian Li; Fan Lu; Wan-Hao Cai; Hui-Li Wang (Food Chemistry, 2024)

Microfluidic paper-based analysis device applying black phosphorus nanosheets@MWCNTs-COOH: A portable and efficient strategy for detection of β-Lactoglobulin in dairy products - Xintong Han; Dan Zhang; Mengjiao Xie; Jingying Yang; Yueyao Wang; Huilin Li; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

Bimetallic Ag/Au nanoclusters encapsulated in ZIF-8 framework: A novel strategy for ratiometric fluorescence detection of doxycycline in food - Yueyao Wang; Mengmeng Gao; Jingying Yang; Huilin Li; Xintong Han; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

High-density mapping of durable and broad-spectrum stripe rust resistance gene Yr30 in wheat - Xiaoting Wang; Mingjie Xiang; Huaizhou Li; Xiaoxiao Li; Keqing Mu; Shuo Huang; Yibo Zhang; Xiangrui Cheng; Shuqing Yang; Xunying Yuan; Ravi P. Singh; Sridhar Bhavani; et al. (Theoretical and Applied Genetics, 2024)

Corrigendum to “Elimination of Microcystis aeruginosa through Leuconostoc mesenteroides DH and its underlying mechanism” [Sci. Total Environ. 908 (2024) 168290] - Yi Li; Mengyuan Qin; Shuo Han; Yuqi Wang; Chao Gao; Wenfang Niu; Xiaohua Xia (Science of The Total Environment, 2024)

Enzyme-free intelligent films in electrochemistry of malathion with a binary architecture: Combined Cu2+ complexed carbon nitride nanosheets and poly(N,N-dimethylacrylamide) hydrogels - Xinyu Wang; Jiping Han; Ke Zhang; Ying Liu; Changyi Yang; Keren Shi; Lingchen Meng; Shuo Gu; Huiqin Yao (Journal of Environmental Chemical Engineering, 2024)

Biofilm formation of Hafnia paralvei induced by c-di-GMP through facilitating bcsB gene expression promotes spoilage of Yellow River carp (Cyprinus carpio) - Mengyuan Qin; Shuo Han; Miaomiao Chen; Pengju Li; Yuqi Wang; Wenfang Niu; Chao Gao; Hailei Wang; Yi Li (Food Microbiology, 2024)

Phosphine oxide balanced charge transfer hybridization in multi-resonance emitters: towards ∼40% external quantum efficiency and preserved color purity - Su Chen; Yidan Wang; Jincheng Lin; Rundong Tian; Shuang Li; Yi Man; Shuo Chen; Jing Zhang; Chunbo Duan; Chunmiao Han; Hui Xu (Chemical Engineering Journal, 2024)

Integrated Metagenomics and 15N Isotope Tracing Reveal the Mechanisms Through which the Nitrogen-Planting Density Interaction Impacts Rice Root Nitrogen Uptake Efficiency - Changhui Sun; Yanyao Lu; Guoping Tang; Runnan Wang; Han Wu; Jiao Zhang; Shuo Cai; Jinyan Zhu; Qiangqiang Xiong (Journal of Soil Science and Plant Nutrition, 2024)

Dynamic response and performance assessment of subsea sandwich pipelines with different interlayer subjected to underwater explosion - Hong Lin; Hao Xu; Lei Yang; Pingping Han; Shuo Zhang; Longcheng Wei; Guoming Chen (Process Safety and Environmental Protection, 2024)

Polystyrene microplastics promote intestinal colonization of Aeromonas veronii through inducing intestinal microbiota dysbiosis - Yuqi Wang; Chao Gao; Wenfang Niu; Shuo Han; Mengyuan Qin; Zhuo Tian; Wenjing Zuo; Xiaohua Xia; Hailei Wang; Yi Li (Journal of Hazardous Materials, 2024)

Fine molecular structure and digestibility changes of potato starch irradiated with electron beam and X-ray - Xiaoqing Lei; Jiayi Xu; Hui Han; Xiaolu Zhang; Yihan Li; Shuo Wang; Yali Li; Yamei Ren (Food Chemistry, 2024)

A hydrological process-based neural network model for hourly runoff forecasting - Shuai Gao; Shuo Zhang; Yuefei Huang; Jingcheng Han; Ting Zhang; Guangqian Wang (Environmental Modelling & Software, 2024)

Effects of geometric structures on the sub-Kelvin porous media heat exchanger - Xue-shuo Shang; Han Gong; Xiao-xin Zeng; Bing-cheng Wang; Huai-qing Cao; Wei Shao; Zheng Cui (International Journal of Refrigeration, 2024)

Synchronous fluorescence spectra-based machine learning algorithm with quick and easy accessibility for simultaneous quantification of polycyclic aromatic hydrocarbons in edible oils - Jia-Wen Wei; Jia-Rong He; Shi-Yi Chen; Yi-Han Guo; Xuan-Zhu Huo; Nuan Zheng; Shuo-Hui Cao; Yao-Qun Li (Food Control, 2024)

Ascertaining sensitive exposure biomarkers of various metal(loid)s to embryo implantation - Mengyuan Ren; Tianxiang Wu; Shuo Yang; Ning Gao; Changxin Lan; Han Zhang; Weinan Lin; Shu Su; Lailai Yan; Lili Zhuang; Qun Lu; Jia Xu; et al. (Environmental Pollution, 2024)

Hsa-miR-877-5p Expression in Acute Ischemic Stroke Based on Bioinformatics Analysis and Clinical Validation - Si-Shuo Zhang; Ji-Wei Zhang; Kai-Xin Zhang; Wen-Qiang Cui; Hong-Wei Zhi; Hai-Tao Li; Hong-Yun Wu; Ya-Han Wang (Molecular Neurobiology, 2024)

Finite Element Analysis of Percutaneous Anterograde and Retrograde Screws in the Treatment of Superior Rami Pubis Fracture - Hui Lu; Shuo Han; Zheng Lian; Rong Liu; Xuexiao Ma (Journal of Medical and Biological Engineering, 2024)
Purpose This study aims to evaluate the biomechanical characteristics of percutaneous antegrade and retrograde screws in treating superior pubic rami fractures in zone II, employing finite element analysis. It provides a theoretical basis for the treatment of the superior rami of pubis zone II fracture. Methods The software of Mimics and 3-Matic were utilized for reconstructing a fracture model of the superior pubic rami in zone II. Percutaneous screw implantation was simulated for treatment. Material properties were assigned using Mimics, and Ansys software was employed to simulate forces on the S1 vertebral endplate under a 500 N load in a standing posture. Mechanical stability was assessed by comparing these simulations. Results (1) Displacement and stress variations in the pubic bone and screws were consistent across the model and on the fracture site, whether the fracture was in zone I or zone II. However, in zone III, the displacement and stress experienced by the screws were markedly higher than those in zones I and II. (2) When employing an antegrade screw to simulate treatment of a superior pubic rami fracture in zone II, the maximum displacement and stress recorded were 0.88 mm and 15.53 MPa, respectively. Conversely, the use of a retrograde screw for treating a superior pubic rami fracture yielded a maximum displacement of 0.59 mm and stress of 5.51 MPa. Conclusion The biomechanical analysis suggests that for zone II superior pubic rami fractures, where the fracture line is no more than 70 mm from the insertion point (encompassing zones I and II fractures), the use of retrograde screw implantation is preferable.

Low-blank method for the offline batch analysis of the low concentration of dissolved lead in natural waters and its application to natural waters, including the tropical Northwest Pacific Ocean - Shuo Jiang; Jing Zhang; Zheng Bo Liu; Han Su (Marine Chemistry, 2024)

Quorum sensing signal autoinducer-2 promotes hydrogen peroxide degradation in water by Gram-positive bacteria - Shuo Han; Mengyuan Qin; Yuqi Wang; Chao Gao; Wenfang Niu; Jingjing Han; Hailei Wang; Yi Li (Journal of Hazardous Materials, 2024)

Development of pH-responsive intelligent and active films based on pectin incorporating Schiff base (Phenylalanine/syringaldehyde) for monitoring and preservation of fruits - Shuo Mao; Linli Zhang; Jingyi Feng; Ping Han; Chengwen Lu; Tiehua Zhang (Food Chemistry, 2024)

Electron beam irradiation pretreatment for efficient extraction of pectin from spaghetti squash peel: Structural, functional, and biological properties - Hui Han; Yi Luo; Junqing Bai; Ze Tao; Shuo Wang; Xiaoqing Lei; Yuxin Feng; Yamei Ren (Food Hydrocolloids, 2024)

Recent advances in electrospinning-nanofiber materials used in advanced oxidation processes for pollutant degradation - Heshan Zheng; Han Lu; Shuo Li; Junfeng Niu; Yoong Kit Leong; Wen Zhang; Duu-Jong Lee; Jo-Shu Chang (Environmental Pollution, 2024)

Trussed concrete-filled steel tubular hybrid structures subjected to axial compression: Performance and design calculation - Zhan-Shuo Liang; Lin-Hai Han (Engineering Structures, 2024)

Accelerating the generation of NiOOH by in-situ surface phosphating nickel sulfide for promoting the proton-coupled electron transfer kinetics of urea electrolysis - Xin Guo; Longyu Qiu; Menggang Li; Fenyang Tian; Xue Ren; Sheng Jie; Shuo Geng; Guanghui Han; Yarong Huang; Ying Song; Weiwei Yang; Yongsheng Yu (Chemical Engineering Journal, 2024)

An effective pharmacological hydrogel induces optic nerve repair and improves visual function - Lipeng Wang; Shan Zhang; Yawen Han; Shuo Tang; Jiarui Li; Lina Bu; Dongyu Zhao; Hongkui Deng (Science China Life Sciences, 2024)

The multi-scale structure changes of γ-ray irradiated potato starch to mitigate pasting/digestion properties - Xiaoqing Lei; Shuo Wang; Yali Li; Hui Han; Xinying Zhang; Xiaoyun Mao; Yamei Ren (Food Research International, 2024)

Carbon dots-based fluorescent molecularly imprinted photonic crystal hydrogel strip: Portable and efficient strategy for selective detection of tetracycline in foods of animal origin - Mingfei Pan; Yueyao Wang; Jingying Yang; Huilin Li; Xintong Han; Shuo Wang (Food Chemistry, 2024)

Magnetic-fluorescent immunosensing platform applying AuNPs heterogeneous MIL-53(Al) composite for efficient detection of zearalenone - Huilin Li; Jingying Yang; Ran Han; Yueyao Wang; Xintong Han; Shuo Wang; Mingfei Pan (Food Chemistry, 2024)

N-acyl-homoserine lactones-mediated quorum sensing promotes intestinal colonization of Aeromonas veronii through facilitating cheA gene expression - Yi Li; Yuqi Wang; Shuo Han; Mengyuan Qin; Xiaomin Wu; Wenfang Niu; Chao Gao; Hailei Wang (Aquaculture, 2024)

Elimination of Microcystis aeruginosa through Leuconostoc mesenteroides DH and its underlying mechanism - Yi Li; Mengyuan Qin; Shuo Han; Yuqi Wang; Chao Gao; Wenfang Niu; Xiaohua Xia (Science of The Total Environment, 2024)

Tetracycline inhibits the nitrogen fixation ability of soybean (Glycine max (L.) Merr.) nodules in black soil by altering the root and rhizosphere bacterial communities - Shuo Zhang; Wei Han; Tianqi Liu; Chengcheng Feng; Qun Jiang; Bo Zhang; Yukun Chen; Ying Zhang (Science of The Total Environment, 2024)

The apoptosis of Chlorella vulgaris and the release of intracellular organic matter under metalimnetic oxygen minimum conditions - Ru Wang; Shuo Wang; Ruihua Cao; Jingru Han; Tinglin Huang; Gang Wen (Science of The Total Environment, 2024)

Evolutionary game analysis of forest carbon note system in China - Qin Qiao; Shuo Lei; Xinting Gao; Yong Sun; Yongwei Han; Zhongrui Sun (Journal of Cleaner Production, 2024)

Beyond fixed-speed pumped storage: A comprehensive evaluation of different flexible pumped storage technologies in energy systems - Ziwen Zhao; Meng Zhang; Mengjiao He; Yuanqiang Gao; Jianling Li; Shuo Han; Zhengguang Liu; Liuwei Lei; Juan I. Pérez Díaz; Giovanna Cavazzini; Diyi Chen (Journal of Cleaner Production, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Green tea polyphenols alleviate β-conglycinin-induced anaphylaxis by modulating gut microbiota in rats - Yang Zhou; Shugui Zheng; Shuo Yang; Jiguang Li; Kai Yang; Junfeng Han; Shuang Duan (Food Bioscience, 2023)

Effects of dry-salting and brine-pickling on physicochemical properties and flavor of spaghetti squash shreds - Yi Luo; Rui Wang; Hui Han; Shuo Wang; Jianxiang Ma; Chunlong Yuan; Yamei Ren (Food Bioscience, 2023)

S-scheme SnO/TiO2 heterojunction with high hole mobility for boosting photocatalytic degradation of gaseous benzene - Shuo Yang; Qipeng Lu; Faguo Wang; Yuanhong Zhi; Jingyue Chen; Yihan Wang; Han Zhang; Haiqing Yin; Peng Sun; Wenbin Cao (Chemical Engineering Journal, 2023)

Remediation of atrazine in environment by persulfate activation via N/B co-doped Si-rich biochar: Performance, mechanisms, degradation pathways and phytotoxicity - Tong Zhang; Hailing Yu; Zhaolian Han; Shuang Xu; Zhihui Dong; Kaishan Zhou; Shuo Zhang; Zhiqiang Cheng (Chemical Engineering Journal, 2023)

Alleviation effect of Deinococcus sp. Y35 together with autoinducer 2 on the physiological stress caused by Microcystis aeruginosa to zebrafish intestines - Shuo Han; Chengjin Lu; Mengyuan Qin; Yuqi Wang; Xiaomin Wu; Xiaohua Xia; Yi Li (Aquaculture, 2023)

Impacts of Nile Tilapia (Oreochromis niloticus) exposed to microplastics in bioflocs system - Xin Hu; Liu-Jiang Meng; Han-Dan Liu; Yan-Shuo Guo; Wen-Chang Liu; Hong-Xin Tan; Guo-Zhi Luo (Science of The Total Environment, 2023)

Economic analysis of global microalgae biomass energy potential - Shuo Yuan; Wenbin Lei; Yu Cen; Qi Liu; Jingping Liu; Jianqin Fu; Yubo Han (Science of The Total Environment, 2023)

The novel lncRNA-9802/miR-1646 axis affects cell proliferation of DF-1 by regulating Bax/Bcl-2 signaling pathway - Shuo Han; Shuang Zhao; Yaolu Zhao; Mingchun Liu; Liping Han; Limei Han (Research in Veterinary Science, 2023)

Regioselective [3 + 2] cycloaddition of diazo reagents and internal alkynes: Accessing regiosomers of highly substituted trifluoromethylpyrazoles - Shuo-Han Li; Ran Guo; Ning Lv; Yu Liu; Xiaodong Tang; Jun-An Ma (Journal of Fluorine Chemistry, 2023)

Combustion characteristics and misfire mechanism of a passive pre-chamber direct-injection gasoline engine - Hao Zhou; Shuo Meng; Zhiyu Han (Fuel, 2023)

Using automated machine learning techniques to explore key factors in anaerobic digestion: At the environmental factor, microorganisms and system levels - Yi Zhang; Zhangmu Jing; Yijing Feng; Shuo Chen; Yeqing Li; Yongming Han; Lu Feng; Junting Pan; Mahmoud Mazarji; Hongjun Zhou; Xiaonan Wang; Chunming Xu (Chemical Engineering Journal, 2023)

Enzyme-mediated proximity labeling for mapping molecular interactions - Xinrui Fan; Xinwen Yan; Shuo Han (Science China Life Sciences, 2023)

Mangrove forest mapping from object-oriented multi-feature ensemble classification using Sentinel-2 images - Han Zhang; Qing Xia; Shuo Dai; Qiong Zheng; Yunfei Zhang; Xingsheng Deng (Frontiers in Marine Science, 2023)
Accurate mapping of mangrove forests is crucial for understanding their ecosystem function and developing effective management policies. However, the absence of an operational multi-feature fusion approach and an ensemble classification system restricts the achievement of this goal. This study aims to develop an object-oriented multi-feature ensemble classification scheme (OMEC). First, an enhanced mangrove spectral index (EMSI) is established by analyzing the spectral reflectance differences between mangrove forests and other land cover types. Sentinel-2 images are segmented into objects using the multi-resolution segmentation method. Then, spectral, textural, and geometric features are extracted, and these features (including EMSI) are inputted into the nearest neighbor classifier to implement mangrove classification. The experiment was conducted in three typical mangrove areas in China using Sentinle-2 images. The results demonstrate that EMSI exhibits good spectral separability for mangroves and performs well in the ensemble classification scheme. The overall accuracy of mangrove classification exceeds 90%, with a Kappa coefficient greater than 0.88. The object-oriented multi-feature ensemble classification scheme significantly improves accuracy and exhibits excellent performance. The method enhances the accuracy of mangrove classification, enriches the approach to mangrove remote sensing interpretation, and offers data support and scientific references for the restoration, management, and protection of coastal wetlands.

High-throughput horticultural phenomics: The history, recent advances and new prospects - Moran Zhang; Shengyong Xu; Yutong Han; Dongping Li; Shuo Yang; Yuan Huang (Computers and Electronics in Agriculture, 2023)

SIRT1 reduction contributes to doxorubicin–induced oxidative stress and meiotic failure in mouse oocytes - Jun Han; Shuo Wang; Huarong Wang; Tuo Zhang; Ye Yang; Ting Zhao; Ziqi Chen; Guoliang Xia; Chao Wang (Toxicology and Applied Pharmacology, 2023)

Biochar application promotes crops yield through regulating root development and the community structure of root endophytic fungi in wheat-maize rotation - Shuo Han; Hongbo Li; Zed Rengel; Zhangliu Du; Ning Hu; Yanan Wang; Aiping Zhang (Soil and Tillage Research, 2023)

Portable smartphone-assisted fluorescence-colorimetric multidimensional immunosensing microarray based on NH2-UiO-66@PtNPs multifunctional composite for efficient and visual detection of amantadine - Huilin Li; Jingying Yang; Xiaochun Hu; Ran Han; Shuo Wang; Mingfei Pan (Chemical Engineering Journal, 2023)

Hippocampal LIMK1-mediated Structural Synaptic Plasticity in Neurobehavioral Deficits Induced by a Low-dose Heavy Metal Mixture - Fankun Zhou; Lu Ouyang; Qi Li; Shuo Yang; Sisi Liu; Han Yu; Qiyue Jia; Shaoqi Rao; Jie Xie; Guihua Du; Chang Feng; Guangqin Fan (Molecular Neurobiology, 2023)

Identification and application of species-specific peptide biomarkers from soft-shelled turtles (Pelodiscus sinensis) using post-translational modification detection-based peptidomics analysis - Haoran Xia; Xun Liu; Shuo Cai; Shengjun Chen; Song Li; Ming Zhao; Jin-ao Duan; Rui Liu; Shuying Han (Food Chemistry, 2023)

Multifunctional composite membranes for interfacial solar steam and electricity generation - Yiting Wu; Jianqiushi Ma; Shuo Zang; Weiming Zhou; Zequn Wang; Minsu Han; Sameh M. Osman; Chong Wang; Yusuke Yamauchi; Jungmok You; Meng An; Liwei Wang; et al. (Chemical Engineering Journal, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

The gas bearing and reservoir characteristics of finely divided lithofacies and dominant lithofacies: an example of Longmaxi Formation shale in northern Yunnan-Guizhou - Geng Liu; Changcheng Han; Shuo Feng; Ning Lv; Ming Qi (Arabian Journal of Geosciences, 2023)

Blue/red dual emission based ratiometric fluorescent intelligent labels for real-time food freshness monitoring - Shuo Yang; Jiang Lou; Limin Jing; Qijun Ding; Xia Li; Yifei Jiang; Zhuqing Liu; Wenjia Han (Food Control, 2023)

Design of red-emitting 1D zinc coordination polymer for targeted drug delivery to nucleus - Shuo Xiang; Jia Liu; Guangze Han; Wei Zhang; Yanyang Long; Yuxian Deng; Binju Wang; Qunhong Weng (Chemical Engineering Journal, 2023)

Enhancing nitrate attenuation in groundwater via selectively applying surface agricultural practices: A novel and sustainable strategy for non-point source pollution mitigation - Linna Jia; Jia Xin; Han Wu; Shuo Gong; Haoran Wu; Zhiyuan Zhang (Water Research, 2023)

Trace metals and nutrients in tropical volcanic island rivers: Insights on chemical weathering and anthropogenic influences of Pohnpei, Micronesia - Han Su; Shan Jiang; Xiaodao Wei; Jie Jin; Yan Chang; Shuo Jiang; Xin Shi; Zheng Bo Liu; Jing Zhang (Limnologica, 2023)

Mineralogical characteristics of root iron plaque and its functional mechanism for regulating Cr phytoextraction of hyperaccumulator Leersia hexandra Swartz - Xuehong Zhang; Chang Su; Yuanyuan Zhang; Simin Lai; Shuo Han; Xingran Zhang; Junjian Zheng (Environmental Research, 2023)

Effect of boron and nitrogen modulation in metal atoms anchoring on flower-like carbon superstructure for efficient ammonia electrosynthesis - Yanchao Zhao; Shuo Zhang; Cong Han; Qian Lu; Qiuju Fu; Huimin Jiang; Lingzhi Yang; Yanlong Xing; Qiuju Zheng; Jianxing Shen; Liting Yan; Xuebo Zhao (Chemical Engineering Journal, 2023)

Review: Synthesis of metal organic framework-based composites for application as immunosensors in food safety - Mingfei Pan; Huilin Li; Jingying Yang; Yixin Wang; Yueyao Wang; Xintong Han; Shuo Wang (Analytica Chimica Acta, 2023)

Carbon and H2 recoveries from plastic waste by using a metal-free porous biocarbon catalyst - Yanghao Jin; Hanmin Yang; Shuo Guo; Ziyi Shi; Tong Han; Ritambhara Gond; Pär G. Jönsson; Weihong Yang (Journal of Cleaner Production, 2023)

Research on Seabed Sediment Classification Based on the MSC-Transformer and Sub-Bottom Profiler - Han Wang; Qingjie Zhou; Shuo Wei; Xiangyang Xue; Xinghua Zhou; Xiaobo Zhang (Journal of Marine Science and Engineering, 2023)
This paper proposed an MSC-Transformer model based on the Transformer’s neural network, which was applied to seabed sediment classification. The data came from about 2900 km2 of seabed area on the northern slope of the South China Sea. Using the submarine backscattering intensity and depth data obtained by the sub-bottom profiler, combined with latitude and longitude information, a seabed dataset of the slope area of the South China Sea was constructed. Moreover, using the MSC-Transformer, the accurate identification and judgment of sediment types such as calcareous bio-silt, calcareous bio-clay silt, silty sand, medium sand and gravel sand were realized. Compared with the conventional deep neural network CNN, RNN, etc., the model shows advantages when applied to the sediment dataset of the shallow sea slope region of the South China Sea. This confirms the feasibility and validity of the model and provides a reliable and accurate tool for seabed sediment classification in the field of marine science. The completeness and accuracy of the dataset and the good performance of the model provide a solid foundation for the scientificalness and practicability of the study.

A 90-Day Prognostic Model Based on the Early Brain Injury Indicators after Aneurysmal Subarachnoid Hemorrhage: the TAPS Score - Runting Li; Fa Lin; Yu Chen; Junlin Lu; Heze Han; Li Ma; Yahui Zhao; Debin Yan; Ruinan Li; Jun Yang; Shihao He; Zhipeng Li; et al. (Translational Stroke Research, 2023)

The change of amino acids samples under metalimnetic oxygen minimum condition: Characterization and mechanism - Na Zhao; Ruihua Cao; Jingru Han; Shuo Wang; Huining Xu; Jingyi Wang; Tinglin Huang; Gang Wen (Journal of Hazardous Materials, 2023)

High density mapping of wheat stripe rust resistance gene QYrXN3517-1BL using QTL mapping, BSE-Seq and candidate gene analysis - Shuo Huang; Yibo Zhang; Hui Ren; Xin Zhang; Rui Yu; Shengjie Liu; Qingdong Zeng; Qilin Wang; Fengping Yuan; Ravi P. Singh; Sridhar Bhavani; Jianhui Wu; et al. (Theoretical and Applied Genetics, 2023)

A Data-Driven Intelligent Prediction Approach for Collision Responses of Honeycomb Reinforced Pipe Pile of the Offshore Platform - Lei Yang; Hong Lin; Chang Han; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2023)
The potential collision between the ship and the pipe piles of the jacket structure brings huge risks to the safety of an offshore platform. Due to their high energy-absorbing capacity, honeycomb structures have been widely used as impact protectors in various engineering applications. This paper proposes a data-driven intelligent approach for the prediction of the collision response of honeycomb-reinforced structures under ship collision. In the proposed model, the artificial neural network (ANN) is combined with the dynamic particle swarm optimization (DPSO) algorithm to predict the collision responses of honeycomb reinforced pipe piles, including the maximum collision depth (δmax) and maximum absorption energy (Emax). Furthermore, a data-driven evaluation method, known as grey relational analysis (GRA), is proposed to evaluate the collision responses of the honeycomb-reinforced pipe piles of offshore platforms. Results of the case study demonstrate the accuracy of the DPSO-BP-ANN model, with measured mean-square-error (MSE) of 5.06 × 10−4 and 4.35 × 10−3 and R2 of 0.9906 and 0.9963 for δmax and Emax, respectively. It is shown that the GRA method can provide a comprehensive evaluation of the performance of a honeycomb structure under impact loads. The proposed model provides a robust and efficient assessment tool for the safe design of offshore platforms under ship collisions.

Metal organic frameworks derived functional materials for energy and environment related sustainable applications - Xihan Tan; Shuo Wang; Ning Han (Chemosphere, 2023)

Life cycle carbon emissions from road infrastructure in China: A region-level analysis - Yuzhao Han; Hui Li; Jiawen Liu; Ning Xie; Ming Jia; Yang Sun; Shuo Wang (Transportation Research Part D: Transport and Environment, 2023)

Multichannel nerve conduit based on chitosan derivates for peripheral nerve regeneration and Schwann cell survival - Zhiwen Jiang; Yijie Zhang; Yanting Wang; Shuo Wang; Jing Chang; Wanshun Liu; Baoqin Han (Carbohydrate Polymers, 2023)

Dexamethasone affects the chemotaxis and phagocytic activity of neutrophils for boar spermatozoa and the quality of liquid preserved boar semen in vitro - Jing-Chun Li; Shuo Wang; He-Chuan Wang; Qun Zhang; Qian Wang; Ming-Hui Guo; Han Zhang; Tian-Feng Li; Qing Guo; Yan-Bing Li; Guo-Sheng Wei (Theriogenology, 2023)

The involvement of AtMKK1 and AtMKK3 in plant-deleterious microbial volatile compounds-induced defense responses - Ching-Han Chang; Wu-Guei Wang; Pei-Yu Su; Yu-Shuo Chen; Tri-Phuong Nguyen; Jian Xu; Masaru Ohme-Takagi; Tetsuro Mimura; Ping-Fu Hou; Hao-Jen Huang (Plant Molecular Biology, 2023)

QTL analyses of soybean root system architecture revealed genetic relationships with shoot-related traits - Zhili Wang; Cheng Huang; Yongchao Niu; Wai-Shing Yung; Zhixia Xiao; Fuk-Ling Wong; Mingkun Huang; Xin Wang; Chun-Kuen Man; Ching-Ching Sze; Ailin Liu; Qianwen Wang; et al. (Theoretical and Applied Genetics, 2022)

Numerical Investigation on Performance Optimization of Offshore Sandwich Blast Walls with Different Honeycomb Cores Subjected to Blast Loading - Hong Lin; Chang Han; Lei Yang; Lin Zhang; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
As an important protective facility on offshore platform, the blast wall is of great significance in resisting oil and gas explosions. Honeycomb structures are widely used due to their unique deformation and mechanical properties under dynamic impact loads. The aim of this research is to develop an optimized design for an offshore sandwich blast wall with different honeycomb cores. The uniqueness of this paper is providing the quantitative optimization scheme for topological configurations and unit cell geometric parameters of honeycomb structures according to mass consistency and the proposed synthetic evaluation index of anti-blast performance. By using the numerical simulation software ANSYS/LS-DYNA, the CONWEP algorithm was first validated and then adopted to conduct the dynamical performance analysis of the honeycomb blast wall. For comparison purposes, simulating studies on a series of different blast walls were carried out by considering various influential parameters. According to different criteria, the blast resistance of the sandwich honeycomb structures was evaluated. It is found that the sandwich plate with concave arc honeycomb core has the best anti-blast performance compared to that of arrow honeycomb core and concave hexagonal honeycomb core. For the concave arc honeycomb structure, the geometric parameters such as concave angle and aspect ratio of honeycomb unit cell have great influence on the blast-resistance performance. Moreover, the concave arc honeycomb structure with positive gradient arrangement has better anti-blast performance than the negative one. The curved blast wall with the curvature of 1/20 achieves better anti-blast performance than the flat blast wall.

Dynamic Performance and Crashworthiness Assessment of Honeycomb Reinforced Tubular Pipe in the Jacket Platform under Ship Collision - Hong Lin; Chang Han; Lei Yang; Hassan Karampour; Haochen Luan; Pingping Han; Hao Xu; Shuo Zhang (Journal of Marine Science and Engineering, 2022)
The collision between the pipe legs of jacket platforms and bypassing ships is of great concern for the safety assessment of platforms. Honeycomb structures have been widely used owing to their unique deformation and mechanical properties under dynamic impact loads. In this paper, two typical honeycomb structures, namely hexagonal honeycomb and arrow honeycomb, were constructed for the impact protection of inclined pipe legs in jacket platforms, and the present study aimed to assess the dynamical performance and crushing resistance of the designed honeycomb reinforced structure under ship collision by using the numerical simulation software ANSYS/LS-DYNA. The dynamical performance of the honeycomb reinforced pipe leg was investigated considering various influential parameters, including the impact velocity and impact direction. The crashworthiness of the two types of honeycomb was evaluated and compared by different criteria, namely the maximum impact depth (δmax), specific energy absorption (SEA) and the proposed index offset sliding (OS). The results demonstrated that both the hexagonal honeycomb structure and the arrow honeycomb structure can reduce the damage of inclined pipe legs caused by ship collision, while the hexagonal honeycomb can provide the better anti-collision capacity, which can well reduce the offset sliding and better protect the pipe leg from ship collision.

Epistatic interaction effect between chromosome 1BL (Yr29) and a novel locus on 2AL facilitating resistance to stripe rust in Chinese wheat Changwu 357-9 - Shuo Huang; Yibo Zhang; Hui Ren; Xiang Li; Xin Zhang; Zeyuan Zhang; Chuanliang Zhang; Shengjie Liu; Xiaoting Wang; Qingdong Zeng; Qilin Wang; Ravi P. Singh; et al. (Theoretical and Applied Genetics, 2022)

Characteristics of a capnophilic small colony variant of Escherichia coli co-isolated with two other strains from a patient with bacteremia in China - Shuo Gao; Zhifeng Zhang; Xuejing Xu; Hui Zhou; Hong Zhu; Yan Zhang; Xiaoli Cao; Wanqing Zhou; Han Shen (Archives of Microbiology, 2022)

The Possible Mechanism of Physiological Adaptation to the Low-Se Diet and Its Health Risk in the Traditional Endemic Areas of Keshan Diseases - Qin Wang; Shuo Zhan; Feng Han; Yiqun Liu; Hongying Wu; Zhenwu Huang (Biological Trace Element Research, 2022)

Measurement of atmospheric conductivity on the Qinghai-Tibet Plateau in China - Lei Li; Jianfeng Su; Tao Chen; Shuo Ti; Han Wu; Jing Luo; Wen Li; Renkang Li (Meteorology and Atmospheric Physics, 2022)

OTNet: A CNN Method Based on Hierarchical Attention Maps for Grading Arteriosclerosis of Fundus Images with Small Samples - Hang Bai; Li Gao; Xiongwen Quan; Han Zhang; Shuo Gao; Chuanze Kang; Jiaqiang Qi (Interdisciplinary Sciences: Computational Life Sciences, 2022)

Effect of Bound Water Content on Secondary Compression of Three Marine Silty Clays - Shuo Li; Changming Wang; Fuyan Guo; Xiaoyang Liu; Songling Han; Ruiyuan Gao (Journal of Marine Science and Engineering, 2022)
Secondary compression studies can provide insights for evaluating the engineering potential and environmental impact of soil. The objective of this research was to investigate the effect of bound water content on the secondary compression of marine silty clay. To this end, a novel method was established based on thermogravimetric analysis (TGA) to determine the contents and limits of strongly bound water and weakly bound water for three typical marine silty clays including Tianjin mucky silty clay (TJ), Qingdao mucky silty clay (QD), and Weihai silty clay (WH). A total of 17 groups of uniaxial confined compression tests were performed for reconstituted samples at different absolute water contents under the condition of multistage loading to investigate their secondary compression characteristics. The results show that the initial dehydration temperature of strongly bound water (Ts) corresponds to the peak of the derivative thermogravimetry (DTG) curve. The values of Ts for TJ, QD and WH are 112.35 °C, 109.67 °C and 118.46 °C, respectively. The initial dehydration temperatures of weakly bound water (Tw) for TJ, QD and WH are 55.26 °C, 52.56 °C and 56.56 °C, respectively. The secondary compression coefficient Cα changes little before the strongly bound water limit and increases dramatically as weakly bound water content increases at the same vertical stress. A piecewise linear model and a quadratic polynomial model are established for calculating the average secondary compression coefficient from bound water content. Weakly bound water is the determining factor controlling secondary compression. Increasing the bound water content weakens the connection force and friction force among the particles and the viscosity of weakly bound water. The results will guide decisions on long-term settlement assessment and facilitate understanding of the secondary compression mechanism of marine silty clays affected by bound water.

Enhanced stripe rust resistance obtained by combining Yr30 with a widely dispersed, consistent QTL on chromosome arm 4BL - Shengjie Liu; Xiaoting Wang; Yayun Zhang; Yangang Jin; Zhonghua Xia; Mingjie Xiang; Shuo Huang; Linyi Qiao; Weijun Zheng; Qingdong Zeng; Qilin Wang; Rui Yu; et al. (Theoretical and Applied Genetics, 2022)

Near-epicenter weather conditions several hours before strong earthquakes (Ms ≥ 6) - Tao Chen; Lei Li; Xiao-Xin Zhang; Qi-Ming Ma; Wen Li; Shuo Ti; Han Wu; Ren-Kang Li; Jing Luo; Jian-Feng Su (Natural Hazards, 2022)

Characterization of EGR-1 Expression in the Auditory Cortex Following Kanamycin-Induced Hearing Loss in Mice - Man Wang; Yuechen Han; Xue Wang; Shuo Liang; Chuan Bo; Zhenbiao Zhang; Mingming Wang; Lei Xu; Daogong Zhang; Wenwen Liu; Haibo Wang (Journal of Molecular Neuroscience, 2021)

A comprehensive exploration on pollution characteristics and health risks of potentially toxic elements in indoor dust from a large Cu smelting area, Central China - Han-Zhi Wang; Li-Mei Cai; Shuo Wang; Guo-Cheng Hu; Lai-Guo Chen (Environmental Science and Pollution Research, 2021)

Mutation of the sixth amino acid of the Rep protein has no effect on porcine circovirus 2b but enhances porcine circovirus 2d replication in vitro - Xiaoyan Wu; Shuo Wang; Changxun Xin; Chen Li; Jianli Shi; Zhe Peng; Chang Liu; Hong Han; Ying Yang; Yao Tian; Jiaxin Li; Shaojian Xu; et al. (Archives of Virology, 2021)

Complement C3 Aggravates Post-epileptic Neuronal Injury Via Activation of TRPV1 - Guang-Tong Jiang; Lin Shao; Shuo Kong; Meng-Liu Zeng; Jing-Jing Cheng; Tao-Xiang Chen; Song Han; Jun Yin; Wan-Hong Liu; Xiao-Hua He; Yu-Min Liu; Lanzi Gongga; et al. (Neuroscience Bulletin, 2021)

Low-Se Diet Can Affect Sperm Quality and Testicular Glutathione Peroxidase-4 activity in Rats - Qin Wang; Shuo Zhan; Yiqun Liu; Feng Han; Lili Shi; Chao Han; Weipeng Mu; Jizhong Cheng; Zhen-wu Huang (Biological Trace Element Research, 2021)

Aspergillus fumigatus Induces the Release of IL-8 and MCP-1 by Activating Nuclear Transcription Through Dectin-1 and CR3 Receptors in Alveolar Epithelial Cells - Yanxi Liu; Zhiqian Li; Shuo Wang; Changjian Zhang; Li Han; Qun Sun; Xuelin Han (Current Microbiology, 2021)

Correction to: Activation of Sigma-1 Receptor Enhanced Pericyte Survival Via the Interplay between Apoptosis and Autophagy: Implications for Blood–Brain Barrier Integrity in Stroke - Yuan Zhang; Xiaotian Zhang; Qiangqiang Wei; Shuo Leng; Cai Li; Bing Han; Ying Bai; Huibin Zhang; Honghong Yao (Translational Stroke Research, 2021)

Refined mapping of stripe rust resistance gene YrP10090 within a desirable haplotype for wheat improvement on chromosome 6A - Shengjie Liu; Shuo Huang; Qingdong Zeng; Xiaoting Wang; Rui Yu; Qilin Wang; Ravi P. Singh; Sridhar Bhavani; Zhensheng Kang; Jianhui Wu; Dejun Han (Theoretical and Applied Genetics, 2021)

A cloud classification method based on random forest for FY-4A - Zhuofu Yu; Shuo Ma; Ding Han; Guanlin Li; Ding Gao; Wei Yan (International Journal of Remote Sensing, 2021)

Estimating cloud base height from Himawari-8 based on a random forest algorithm - Zhonghui Tan; Juan Huo; Shuo Ma; Ding Han; Xin Wang; Shensen Hu; Wei Yan (International Journal of Remote Sensing, 2021)

Dietary Serine and Sulfate-Containing Amino Acids Related to the Nutritional Status of Selenium in Lactating Chinese Women - Feng Han; Xuehong Pang; Qin Wang; Yiqun Liu; Liping Liu; Yingjuan Chai; Jie Zhang; Shijin Wang; Jiaxi Lu; Licui Sun; Shuo Zhan; Hongying Wu; et al. (Biological Trace Element Research, 2021)

QTL analysis of rice photosynthesis-related traits under the cold stress across multi-environments - Zhaoguo Wang; Shuo Wang; Chunhong Yu; Xiao Han; Detang Zou (Euphytica, 2020)

Adsorptive removal of cationic tricyclic antidepressants using cation-exchange resin - Jong-Won Choi; John Kwame Bediako; Yufeng Zhao; Shuo Lin; Amit Kumar Sarkar; Minhee Han; Myung-Hee Song; Chul-Woong Cho; Yeoung-Sang Yun (Environmental Science and Pollution Research, 2020)

A remote sensing monitoring method for alpine grasslands desertification in the eastern Qinghai-Tibetan Plateau - Qian Kuang; Quan-zhi Yuan; Ji-chong Han; Rong Leng; Yu-shuang Wang; Ke-hong Zhu; Shuo Lin; Ping Ren (Journal of Mountain Science, 2020)

Spatial-temporal characteristics and driving factors of the human health impacts of five industrial aquatic toxic metals in China - Yuanyi Huang; Beihai Zhou; Ruru Han; Xiaohui Lu; Shuo Li; Nan Li (Environmental Monitoring and Assessment, 2020)

Activation of Sigma-1 Receptor Enhanced Pericyte Survival via the Interplay Between Apoptosis and Autophagy: Implications for Blood–Brain Barrier Integrity in Stroke - Yuan Zhang; Xiaotian Zhang; Qiangqiang Wei; Shuo Leng; Cai Li; Bing Han; Ying Bai; Huibin Zhang; Honghong Yao (Translational Stroke Research, 2020)

China’s industrial gray water footprint assessment and implications for investment in industrial wastewater treatment - Yuanyi Huang; Beihai Zhou; Ruru Han; Xiaohui Lu; Shuo Li; Nan Li (Environmental Science and Pollution Research, 2020)

Stripe rust resistance genes in a set of Ethiopian bread wheat cultivars and breeding lines - Zeray Siyoum Gebreslasie; Shuo Huang; Gangming Zhan; Ayele Badebo; Qingdong Zeng; Jianhui Wu; Qilin Wang; Shengjie Liu; Lili Huang; Xiaojing Wang; Zhensheng Kang; Dejun Han (Euphytica, 2020)
Stripe rust caused by Puccinia striiformis f. sp . tritici ( Pst ) is one the most important diseases of wheat in Ethiopia and worldwide. To identify resistance genes, 90 bread wheat lines and 10 cultivars were tested at the seedling stage against one Pst race from Ethiopia and six races from China as well as evaluated for the stripe rust response in an inoculated field nursery at Yangling, Shaanxi province and in a naturally infected field in Jiangyou, Sichuan, China. Resistance genes were postulated using molecular assays for Yr9 , Yr17, Yr18, Yr26, Yr29, Yr36, Yr44 and Yr62. Of the 100 entries tested, 16 had all stage resistance to all races. Molecular markers were positive for Yr9 in five genotypes, Yr17 in 21 genotypes, Yr18 in 27 genotypes, Yr26 in ten genotypes, Yr29 in 22 genotypes, Yr36 in 12 genotypes, Yr44 in 30 genotypes, and Yr62 in 51 genotypes. No line had Yr5 , Yr8 , Yr10 or Yr15 . Complete or all stage resistance was observed in genotypes carrying gene combinations Yr9 + Yr18 + Yr44 + Yr62, Yr29 + Yr62 + Yr26 and Yr9 + Yr17 + Yr26 + Yr44 + Yr62. The results are helpful for developing wheat cultivars with effective and more durable resistance to stripe rust both in China and Ethiopia.

Adsorption Characteristic of Cr(VI) onto Different Activated Coal Fly Ashes: Kinetics, Thermodynamic, Application Feasibility, and Error Analysis - Nannan Wang; Yanhe Han; Shuo Li (Water, Air, & Soil Pollution, 2019)

A major QTL co-localized on chromosome 6BL and its epistatic interaction for enhanced wheat stripe rust resistance - Qingdong Zeng; Jianhui Wu; Shengjie Liu; Shuo Huang; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2019)

Genetic architecture of wheat stripe rust resistance revealed by combining QTL mapping using SNP-based genetic maps and bulked segregant analysis - Jingmei Mu; Shuo Huang; Shengjie Liu; Qingdong Zeng; Miaofei Dai; Qilin Wang; Jianhui Wu; Shizhou Yu; Zhensheng Kang; Dejun Han (Theoretical and Applied Genetics, 2019)

Automated Pathogenesis-Based Diagnosis of Lumbar Neural Foraminal Stenosis via Deep Multiscale Multitask Learning - Zhongyi Han; Benzheng Wei; Stephanie Leung; Ilanit Ben Nachum; David Laidley; Shuo Li (Neuroinformatics, 2018)

Comparative genome-wide mapping versus extreme pool-genotyping and development of diagnostic SNP markers linked to QTL for adult plant resistance to stripe rust in common wheat - Jianhui Wu; Shuo Huang; Qingdong Zeng; Shengjie Liu; Qilin Wang; Jingmei Mu; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

SNP-based pool genotyping and haplotype analysis accelerate fine-mapping of the wheat genomic region containing stripe rust resistance gene Yr26 - Jianhui Wu; Qingdong Zeng; Qilin Wang; Shengjie Liu; Shizhou Yu; Jingmei Mu; Shuo Huang; Hanan Sela; Assaf Distelfeld; Lili Huang; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

Degradation of organics extracted from dewatered sludge by alkaline pretreatment in microbial electrolysis cell - Kai Hu; Lan Xu; Wei Chen; Shuo-qiu Jia; Wei Wang; Feng Han (Environmental Science and Pollution Research, 2018)

Rapid identification of an adult plant stripe rust resistance gene in hexaploid wheat by high-throughput SNP array genotyping of pooled extremes - Jianhui Wu; Shengjie Liu; Qilin Wang; Qingdong Zeng; Jingmei Mu; Shuo Huang; Shizhou Yu; Dejun Han; Zhensheng Kang (Theoretical and Applied Genetics, 2018)

High-efficient n-butanol production by co-culturing Clostridium acetobutylicum and Saccharomyces cerevisiae integrated with butyrate fermentative supernatant addition - Hongzhen Luo; Qingwei Zeng; Shuo Han; Zhaoyu Wang; Qing Dong; Yanhong Bi; Yuping Zhao (World Journal of Microbiology and Biotechnology, 2017)

Antidepressant-Like and Anxiolytic-Like Effects of ZBD-2, a Novel Ligand for the Translocator Protein (18 kDa) - Dong-sheng Wang; Jing Han; Shuo Li; Ting Sun; Yan-yan Guo; Wen-bo Kang; Zhen Tian; Jian-ning Zhao; Gang Liu; Shui-bing Liu; Ming-gao Zhao (NeuroMolecular Medicine, 2017)

Sinomenine attenuates chronic inflammatory pain in mice - Shuo Li; Jing Han; Dong-sheng Wang; Qi Yang; Bin Feng; Wen-bo Kang; Le Yang; Gang Liu; Ming-gao Zhao (Metabolic Brain Disease, 2017)

Echinocystic acid reduces reserpine-induced pain/depression dyad in mice - Shuo Li; Jing Han; Dong-sheng Wang; Bin Feng; Ya-ting Deng; Xin-shang Wang; Qi Yang; Ming-gao Zhao (Metabolic Brain Disease, 2016)

Klf10 regulates odontoblast differentiation and mineralization via promoting expression of dentin matrix protein 1 and dentin sialophosphoprotein genes - Zhuo Chen; Wentong Li; Han Wang; Chunyan Wan; Daoshu Luo; Shuli Deng; Hui Chen; Shuo Chen (Cell and Tissue Research, 2016)

Susceptibility and REF1 Gene Polymorphism Towards Colorectal Cancer - Shibin Yang; Yuanhui Lai; Longbin Xiao; Fanghai Han; Wenhui Wu; Shuo Long; Wenfeng Li; Yulong He (Cell Biochemistry and Biophysics, 2015)

Residues and dissipation of trifloxystrobin and its metabolite in tomatoes and soil - Lin Wang; Wenming Li; Puyu Li; Minghui Li; Shuo Chen; Lijun Han (Environmental Monitoring and Assessment, 2014)

Identification of four genotypes of H3N2 swine influenza virus in pigs from southern China - Jidang Chen; Xinliang Fu; Ye Chen; Shuyi He; Yun Zheng; Zhenpeng Cao; Wenxin Yu; Han Zhou; Shuo Su; Guihong Zhang (Archives of Virology, 2014)

Ischemic Postconditioning Protects the Neurovascular Unit after Focal Cerebral Ischemia/Reperfusion Injury - Dong Han; Shuo Zhang; Bin Fan; Lu-lu Wen; Miao Sun; Hong Zhang; Juan Feng (Journal of Molecular Neuroscience, 2014)

Deletion of RBP-J in dendritic cells compromises TLR-mediated DC activation accompanied by abnormal cytoskeleton reorganization - Yun-Ru Chen; Fan Feng; Li Wang; Shuo-Yao Qu; Zhen-Qiang Zhang; Li Liu; Hong-Yan Qin; Ying-Min Liang; Hua Han (Molecular Biology Reports, 2013)

Inhibition of human lung adenocarcinoma growth using survivint34a by low-dose systematic administration - Yan Shan; Chunting Wang; Li Yang; Li Juan Chen; Hong Xin Deng; Han Shuo Yang; Zhimian Li; Zhiyong Li; Li Pan; Fei Leng; Yuquan Wei (Journal of Biosciences, 2010)

Molecular Cloning and Evolutionary Analysis of Hemoglobin α-Chain Genes in Bats - Yang Liu; Dong Dong; Nai-Jian Han; Hua-Bin Zhao; Jin-Shuo Zhang; Gang Li; Paul A. Racey; Shu-Yi Zhang (Biochemical Genetics, 2009)

Tolerance and accumulation of lead by species of Iris L. - Yu-Lin Han; Su-Zhen Huang; Ji-Guang Gu; Shuo Qiu; Jie-Min Chen (Ecotoxicology, 2008)